Method for manufacturing positive electrode active material

JP2025036692AActive Publication Date: 2025-03-14SEMICON ENERGY LAB CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024231974
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-10-04
Filing Date
2024-12-27
Publication Date
2025-03-14
Estimated Expiration
2040-03-23

AI Technical Summary

Benefits of technology

【0018】 本発明の一態様により、正極活物質の作製方法を提供することができる。また、本発明の一態様により、新規な正極活物質粒子を提供することができる。また、本発明の一態様によって新規な蓄電装置を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025036692000001_ABST
    Figure 2025036692000001_ABST
Patent Text Reader

Abstract

To provide a method for manufacturing a positive electrode active material of a lithium ion secondary battery.SOLUTION: A method for manufacturing a positive electrode active material includes: a first step of placing in a heating furnace, a first container in which a mixture of a lithium oxide, a fluoride and a magnesium compound is put; a second step of bringing the inside of the heating furnace into an oxygen containing atmosphere; and a third step of heating the inside of the heating furnace. The first step and the second step are executed and then, the third step is executed. It is preferable that the inside of the heating furnace is brought into the oxygen containing atmosphere before heating the inside of the heating furnace. It is more preferable that the fluoride is lithium fluoride and the magnesium compound is magnesium fluoride.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] One embodiment of the present invention relates to a method for producing a positive electrode active material, or to an object, a process, a machine, a manufacture, or a composition of matter. Another embodiment of the present invention relates to a semiconductor device, a display device, a light-emitting device, a power storage device, a lighting device, an electronic device, or a manufacturing method thereof.

[0002] In this specification, the term "power storage device" refers to elements and devices in general that have a power storage function, including, for example, storage batteries (also called secondary batteries) such as lithium ion secondary batteries, lithium ion capacitors, all-solid-state batteries, and electric double layer capacitors.

[0003] In addition, in this specification, electronic devices refer to devices in general that have a power storage device, and electro-optical devices that have a power storage device, information terminal devices that have a power storage device, and the like are all electronic devices. [Background technology]

[0004] In recent years, the development of various types of power storage devices, including lithium-ion secondary batteries, lithium-ion capacitors, and air batteries, as well as all-solid-state batteries, has been actively pursued. In particular, the demand for high-output, high-capacity lithium-ion secondary batteries has rapidly expanded in conjunction with the development of the semiconductor industry, and they are now indispensable in the modern information society as a rechargeable energy source, as they are used in portable information terminals such as mobile phones, smartphones, and notebook computers, portable music players, digital cameras, medical equipment, and next-generation clean energy automobiles such as hybrid vehicles (HVs), electric vehicles (EVs), and plug-in hybrid vehicles (PHVs or PHEVs).

[0005] Therefore, in order to improve the cycle characteristics and increase the capacity of lithium ion secondary batteries, improvements in the positive electrode active material have been investigated (Patent Document 1 and Patent Document 2).

[0006] Furthermore, characteristics required of power storage devices include safety in various operating environments and improved long-term reliability. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2012-018914 A [Patent Document 2] JP 2016-076454 A [Non-patent literature]

[0008] [Non-Patent Document 1] Toyoki Okumura et al, “Correlation of lithium ion distribution and X-ray absorption near-edge structure in O3-and O2-lithium cobalt oxides from first-principle calculation”, Journal of Materials Chemistry, 2012, 22, p.17340-17348 [Non-Patent Document 2] Motohashi, T. et al, “Electronic phase diagram of the layered cobalt oxide system LixCoO2(0.0≦x≦1.0)”, Physical Review B, 80(16);165114 Summary of the Invention [Problem to be solved by the invention]

[0009] Lithium-ion secondary batteries and the positive electrode active materials used therein are desired to be improved in various aspects, such as capacity, cycle characteristics, charge / discharge characteristics, reliability, and safety, and the development of lithium composite oxide LiMO2, in which part of LiCoO2 is replaced with a different element, is underway. In addition, the development of a method for producing LiMO2 cheaply and in a short time is desired.

[0010] In view of the above, an object of one embodiment of the present invention is to provide a method for manufacturing a positive electrode active material, a novel positive electrode active material, or a novel power storage device.

[0011] Note that the description of these problems does not preclude the existence of other problems. Note that one embodiment of the present invention does not necessarily solve all of these problems. Note that it is possible to extract problems other than these from the description of the specification, drawings, and claims. [Means for solving the problem]

[0012] One embodiment of the present invention is a method for producing a positive electrode active material, which includes a first step of placing a first container containing a mixture of lithium oxide, fluoride, and a magnesium compound in a heating furnace, a second step of creating an oxygen-containing atmosphere inside the heating furnace, and a third step of heating the inside of the heating furnace, and which performs the third step after performing the first step and the second step.

[0013] Another embodiment of the present invention is a method for producing a positive electrode active material, the method including a first step of placing a first container containing a mixture of lithium oxide, a fluoride, and a magnesium compound in a heating furnace, a second step of evacuating the inside of the heating furnace and then introducing oxygen gas, and a third step of heating the inside of the heating furnace, the third step being performed after the first step and the second step.

[0014] In the above structure, the fluoride is preferably lithium fluoride (LiF).

[0015] In the above configuration, the inside of the heating furnace is preferably heated to 735°C or higher and 1000°C or lower.

[0016] In the above-mentioned structure, the magnesium compound is preferably magnesium fluoride (MgF2).

[0017] In the above configuration, it is preferable that the first container is covered with a lid. Effect of the Invention

[0018] According to one embodiment of the present invention, a manufacturing method of a positive electrode active material can be provided. According to another embodiment of the present invention, a novel positive electrode active material particle can be provided. According to another embodiment of the present invention, a novel power storage device can be provided. [Brief description of the drawings]

[0019] [Figure 1] FIG. 1 is a diagram illustrating an example of a method for producing a positive electrode active material. [Diagram 2] FIG. 2 is a diagram illustrating the results of DSC measurement of a mixture of LiF and MgF2. [Diagram 3] 3A and 3B are diagrams illustrating a method for manufacturing a positive electrode active material of one embodiment of the present invention. [Figure 4] 4A and 4B illustrate a method for manufacturing a positive electrode active material of one embodiment of the present invention. [Diagram 5] 5A and 5B illustrate a method for manufacturing a positive electrode active material of one embodiment of the present invention. [Figure 6] FIG. 6 is a diagram illustrating an example of a method for producing a positive electrode active material. [Figure 7] FIG. 7 is a diagram illustrating an example of a method for producing a positive electrode active material. [Figure 8] FIG. 8 is a diagram illustrating an example of a method for producing a positive electrode active material. [Figure 9] FIG. 9 is a diagram illustrating the crystal structure and magnetism of the positive electrode active material. [Figure 10] FIG. 10 is a diagram illustrating the crystal structure and magnetism of a conventional positive electrode active material. [Figure 11] 11A and 11B are cross-sectional views of an active material layer in which a graphene compound is used as a conductive assistant. [Figure 12] 12A and 12B are perspective views illustrating a coin-type secondary battery. [Figure 13] 13A is a perspective view illustrating a cylindrical secondary battery, FIG. 13B is an exploded perspective view, FIG. 13C is a perspective view of the cylindrical secondary battery, and FIG. 13D is a top view illustrating the cylindrical secondary battery. [Figure 14] 14A and 14B are diagrams illustrating an example of a secondary battery. [Figure 15] 15A, 15B, 15C, and 15D are perspective views illustrating examples of secondary batteries. [Figure 16] 16A and 16B are perspective views illustrating an example of a secondary battery. [Figure 17] 17A and 17B are perspective views illustrating an example of a secondary battery. [Figure 18] FIG. 18 is a perspective view illustrating an example of a secondary battery. [Figure 19] 19A, 19B, and 19C are perspective views for explaining a laminated type secondary battery. [Figure 20] FIG. 20A is a top view illustrating a laminated type secondary battery, and FIG. 20B is a cross-sectional view illustrating the laminated type secondary battery. [Figure 21] FIG. 21 is a diagram showing the external appearance of a secondary battery. [Figure 22] FIG. 22 is a diagram showing the appearance of a secondary battery. [Figure 23] 23A, 23B, and 23C are diagrams illustrating a method for producing a secondary battery. [Figure 24] FIG. 24A is a top view of a bendable secondary battery, and FIGS. 24B, 24C, 24D, and 24E are cross-sectional views for explaining the secondary battery. [Diagram 25] 25A and 25B are perspective views illustrating a bendable secondary battery. [Figure 26]Figures 26A and 26B are oblique views illustrating an example of an electronic device, Figure 26C is an oblique view of a secondary battery, Figure 26D is a diagram illustrating an example of an electronic device, Figure 26E is an oblique view of the secondary battery, and Figures 26F and 26G are diagrams illustrating an example of an electronic device. [Figure 27] 27A and 27B are top views for explaining an example of an electronic device, and FIG. 27C is a block diagram. [Figure 28] FIG. 28 is a diagram illustrating an example of an electronic device. [Figure 29] FIG. 29A is a perspective view of the vehicle, FIG. 29B is a perspective view showing the vehicle during charging, and FIG. 29C is a perspective view for explaining the electric motorcycle. [Diagram 30] 30A and 30B are diagrams illustrating the alumina crucible used during annealing. [Diagram 31] FIG. 31 is a diagram illustrating cycle characteristics according to the embodiment. [Diagram 32] FIG. 32 is a diagram illustrating cycle characteristics according to the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] Hereinafter, the embodiments of the present invention will be described in detail with reference to the drawings. However, the present invention is not limited to the following description, and it will be easily understood by those skilled in the art that the form and details of the present invention can be modified in various ways. Furthermore, the present invention is not to be interpreted as being limited to the description of the embodiments shown below.

[0021] In addition, in crystallography, crystal planes and directions are expressed by adding a superscript bar to the numbers, but in this specification and elsewhere, due to restrictions on notation in applications, crystal planes and directions are expressed by adding a - (minus sign) before the numbers instead of adding a bar above them. Also, individual directions showing directions within a crystal are expressed with [ ], collective directions showing all equivalent directions with < >, individual faces showing crystal faces with ( ), and collective faces with equivalent symmetry with {}.

[0022] In this specification, the atmosphere containing a fluoride refers to an atmosphere of a mixed gas containing a fluoride as at least one of its constituent components.

[0023] (Embodiment 1) An example of a method for producing a lithium composite oxide LiMO2 (M is two or more metals including Co, and there is no particular limitation on the substitution position of the metal) will be described with reference to Fig. 1. The following describes an example of a positive electrode active material having Mg as a metal element other than Co contained in LiMO2.

[0024] First, a halogen source is prepared as a material for the mixture 902. Chloride, bromide, and iodide can be used as the halogen source, but fluoride is preferable. In this embodiment, LiF, which is a fluorine source, is prepared as the halogen source. LiF is preferable because it has a common cation with LiCoO2. LiF can be used as both a lithium source and a fluorine source. LiF is also preferable because it has a relatively low melting point of 848° C. and is easily melted in an annealing step described later. Similarly, MgF2, which can also be used as a fluorine source, is preferable as a magnesium source used for LiMO2. Note that LiCl can also be used as the halogen source, and MgCl2 can also be used as the magnesium source. Note that a combination of a halogen source and a magnesium source having a eutectic point is preferable because a melting point drop described later can be utilized. Note that a halogen source that can be used in one embodiment of the present invention is not limited to LiF and LiCl. Note that a magnesium source that can be used in one embodiment of the present invention is not limited to MgF2 and MgCl2.

[0025] In this specification, the eutectic point refers to the point on the solid-liquid phase curve of two components where the two components completely melt and mix in the liquid state without forming a solid solution. For example, when two metal elements A and B melt, A and B do not form a solid solution but form separate solid phases or form a molecular compound, and A and B are completely soluble in the liquid phase, the mixture of A and B has a melting point lower than the melting point of A or B alone. When a mixture has a certain concentration ratio of A and B, it shows the lowest melting point, and this temperature is called the eutectic point, and this mixture is also called a eutectic mixture. The eutectic point is not limited to two components, but may be three, four, or five or more components.

[0026] In this embodiment, LiF, which is a fluorine source, is prepared as a halogen source, and MgF2 is prepared as a fluorine source and magnesium source (step S11 in FIG. 1). The molar ratio of LiF to MgF2 is preferably LiF:MgF2=u:1 (0≦u≦1.9), more preferably LiF:MgF2=u:1 (0.1≦u≦0.5), and even more preferably LiF:MgF2=u:1 (near u=0.33).

[0027] If the next mixing and grinding step is performed in a wet manner, a solvent is prepared. As the solvent, a ketone such as acetone, an alcohol such as ethanol or isopropanol, ether, dioxane, acetonitrile, N-methyl-2-pyrrolidone (NMP), etc. can be used. It is more preferable to use an aprotic solvent that does not easily react with lithium. In this embodiment, acetone is used (see step S11 in FIG. 1).

[0028] Next, the materials of the mixture 902 are mixed and pulverized (step S12 in FIG. 1). Mixing can be performed in a dry or wet manner, but the wet method is preferred because it allows for finer pulverization. For example, a ball mill, a bead mill, etc. can be used for mixing. When using a ball mill, it is preferable to use zirconia balls, for example, as the media. It is preferable to thoroughly perform this mixing and pulverization process to finely pulverize the mixture 902.

[0029] The mixed and crushed materials are collected (step S13 in FIG. 1), and a mixture 902 is obtained (step S14 in FIG. 1).

[0030] The mixture 902 preferably has an average particle size (D50) of, for example, 600 nm to 20 μm, more preferably 1 μm to 10 μm. If the mixture 902 is finely pulverized in this way, when it is mixed with a composite oxide having lithium, transition metal, and oxygen, such as lithium cobalt oxide, in a later process, the mixture 902 can be easily attached uniformly to the surface of the composite oxide particles. If the mixture 902 is attached uniformly to the surface of the composite oxide particles, it is preferable because it is easy to distribute halogen and magnesium thoroughly in the surface layer of the composite oxide particles after heating. If there is a region in the surface layer that does not contain halogen and magnesium, it may be difficult to form a pseudo-spinel type crystal structure described later in the charged state.

[0031] <Step S25> Next, a lithium source is prepared as shown in step S25. In step S25, a composite oxide having lithium, a transition metal, and oxygen that has been synthesized in advance is used.

[0032] When using a composite oxide having lithium, transition metals, and oxygen that has been synthesized in advance, it is preferable to use one with few impurities. In this specification, the main components of the composite oxide having lithium, transition metals, and oxygen, and the positive electrode active material are lithium, cobalt, nickel, manganese, aluminum, and oxygen, and elements other than the main components are impurities. For example, when analyzed by glow discharge mass spectrometry (GD-MS), the total impurity concentration is preferably 10,000 ppm wt or less, more preferably 5000 ppm wt or less. In particular, the total impurity concentration of transition metals such as titanium and arsenic is preferably 3000 ppm wt or less, more preferably 1500 ppm wt or less.

[0033] For example, lithium cobalt oxide particles (product name: Cellseed C-10N) manufactured by Nippon Chemical Industry Co., Ltd. can be used as the pre-synthesized lithium cobalt oxide. This is lithium cobalt oxide with an average particle diameter (D50) of about 12 μm, and in impurity analysis by glow discharge mass spectrometry, the magnesium concentration and fluorine concentration are 50 ppm wt or less, the calcium concentration, aluminum concentration and silicon concentration are 100 ppm wt or less, the nickel concentration is 150 ppm wt or less, the sulfur concentration is 500 ppm wt or less, the arsenic concentration is 1100 ppm wt or less, and the concentration of other elements other than lithium, cobalt and oxygen is 150 ppm wt or less.

[0034] The composite oxide having lithium, a transition metal, and oxygen in step S25 preferably has a layered rock-salt type crystal structure with few defects and distortion. Therefore, it is preferable that the composite oxide has few impurities. If the composite oxide having lithium, a transition metal, and oxygen contains a large amount of impurities, it is highly likely that the composite oxide will have a crystal structure with many defects or distortion.

[0035] Next, the mixture 902 is mixed with a composite oxide having lithium, a transition metal, and oxygen (step S31 in FIG. 1). The ratio of the number of transition metal atoms TM in the composite oxide having lithium, a transition metal, and oxygen to the number of magnesium atoms MgMix1 in the mixture 902 is preferably TM:MgMix1=1:v (0.005≦v≦0.05), more preferably TM:MgMix1=1:v (0.007≦v≦0.04), and even more preferably about TM:MgMix1=1:0.02.

[0036] The mixing in step S31 is preferably performed under milder conditions than those in step S12 in order not to destroy the composite oxide particles. For example, the mixing is preferably performed under conditions of a lower rotation speed or shorter time than those in step S12. It can also be said that the dry method is a milder condition than the wet method. For example, a ball mill, a bead mill, etc. can be used for mixing. When using a ball mill, it is preferable to use zirconia balls as the media, for example.

[0037] The mixed materials are collected (step S32 in FIG. 1) to obtain a mixture 903 (step S33 in FIG. 1).

[0038] Next, mixture 903 is heated (step S34 in FIG. 1). This step is sometimes called annealing. LiMO2 is generated by annealing. Therefore, the conditions for performing step S34, such as temperature, time, atmosphere, and the weight of mixture 903 to be annealed, are important. In this specification, annealing also means heating mixture 903 or at least heating a heating furnace in which mixture 903 is placed.

[0039] If the conditions of S34 are not appropriate, a positive electrode active material having good properties may not be obtained. In addition, the processing time of step S34 is often long compared to other steps, and it is possible to produce a positive electrode active material in a short time by shortening the processing time of step S34. Therefore, a technology for shortening the processing time of step S34 is required.

[0040] The present inventors found that a positive electrode active material with good characteristics can be manufactured by performing annealing in an atmosphere containing fluoride (LiF in this embodiment) contained in the mixture 903. In addition, the present inventors found that the annealing time can be shortened according to one embodiment of the present invention.

[0041] [Effect of annealing in a fluoride-containing atmosphere] The annealing temperature is preferably equal to or higher than the temperature at which mixture 902 melts. It is assumed that when mixture 903 is annealed, mixture 902 melts. For example, it is assumed that a mixture of MgF2 (melting point 1263°C) and LiF (melting point 848°C) melts and is distributed in the surface layer of the composite oxide particles. It is assumed that the melting of MgF2 promotes a reaction with LiCoO2, producing LiMO2. Therefore, it is preferable that the fluoride and magnesium source are combined to form a eutectic mixture.

[0042] Moreover, the annealing temperature is more preferably equal to or higher than the temperature at which the mixture 903 melts. It is believed that the formation of LiMO2 is promoted by the fluoride (e.g., LiF), the magnesium source (e.g., MgF2), and the lithium oxide (e.g., LiCoO2) forming a covalent mixture.

[0043] In addition, the annealing temperature must be equal to or lower than the decomposition temperature of LiCoO2 (1130°C). Therefore, it is preferable to heat the material at a temperature equal to or higher than the eutectic point of the fluoride and the magnesium source and equal to or lower than 1130°C.

[0044] As will be described later, the eutectic point of LiF and MgF2 is around 735°C. In addition, LiF, MgF2 and LiCoO2 have endothermic peaks observed around 820°C by differential scanning calorimetry (DSC measurement). Therefore, the annealing temperature is preferably 735°C or higher, more preferably 820°C or higher. In addition, the decomposition temperature of LiCoO2 is 1130°C, but at temperatures around that temperature, there is a concern that LiCoO2 may decompose, albeit in a small amount. Therefore, the annealing temperature is preferably 1130°C or lower, and more preferably 1000°C or lower.

[0045] Therefore, the annealing temperature is preferably 735° C. or higher and 1130° C. or lower, and more preferably 735° C. or higher and 1000° C. or lower. Also, the annealing temperature is preferably 820° C. or higher and 1130° C. or lower, and more preferably 820° C. or higher and 1000° C. or lower.

[0046] Here, the DSC measurement of a mixture of LiF and MgF2 will be described.

[0047] The measurement device used is ThermoplusEV02 manufactured by Rigaku Co., Ltd. The temperature range is from 25°C to 1000°C, and the heating rate is 20°C / min.

[0048] Figure 2 shows the results of DSC measurement of a mixture of LiF and MgF2 (LiF / MgF2 = 0.33 mol%). From Figure 2, an endothermic peak is observed near 735°C. Therefore, the mixture of LiF and MgF2 has a eutectic point near 735°C.

[0049] In addition, in this embodiment, it is considered that LiF, which is a fluoride, functions as a flux. Therefore, when LiF evaporates and the amount of LiF in the mixture 903 decreases, it is expected that MgF2 becomes difficult to melt and the generation of LiMO2 is suppressed. Therefore, it is preferable to heat while suppressing the evaporation of LiF.

[0050] Therefore, by heating the mixture 903 in an atmosphere containing LiF, that is, by heating the mixture 903 in a state where the partial pressure of LiF is high in the heating furnace, the vaporization of LiF in the mixture 903 can be suppressed and the generation of LiMO2 can be efficiently promoted. Therefore, a positive electrode active material with good characteristics can be produced, and the annealing time can also be shortened.

[0051] Here, the weight loss rate can be experimentally investigated when a mixture of LiF and MgF2 (LiF / MgF2 = 0.33 mol%) is heated at a specified temperature. The experimental method is to heat the mixture of LiF and MgF2 to a specified temperature at 200°C / h and maintain the specified temperature for 10 hours. The temperature is then lowered over a period of 10 hours or more. In addition, heating is performed while flowing oxygen at a flow rate of 2.5 L / min. The results of the weight loss rate measurement are shown in Table 1. In Table 1, the weight loss rate (%) is calculated by dividing the weight difference of the mixture before and after heating by the weight of the mixture before heating x 100.

[0052] [Table 1]

[0053] As shown in Table 1, the mixture of LiF and MgF2 shows a weight loss at least at 700°C. Therefore, it is understood that at temperatures of at least 700°C or higher, the components of LiF and MgF2 are vaporized and lost from the reaction system.

[0054] In this specification, a heating furnace is a facility used for heat-treating (annealing) a substance or mixture, and has a heater unit, an atmosphere containing a fluoride, and an inner wall that can withstand at least 600° C. The heating furnace may also be equipped with a pump that has at least one of the functions of reducing and pressurizing the inside of the furnace.

[0055] [Annealing in an atmosphere containing fluoride] An example of a method for performing annealing in a heating furnace with an atmosphere containing a fluoride will be described with reference to FIGS. 3A and 3B.

[0056] The heating furnace 120 shown in Figures 3A and 3B has a heating furnace space 102, a hot plate 104, a heater unit 106, and a heat insulating material 108. Figure 3A shows a state in which a container 116 containing a mixture 903 is placed in the heating furnace space 102. The mixture 903 contains fluoride. Therefore, by heating the mixture 903 and vaporizing a part of the fluoride contained in the mixture 903, the mixture 903 can be heated in an atmosphere containing fluoride.

[0057] Here, the valence of Co (cobalt) in LiMO2 produced by one embodiment of the present invention is preferably trivalent. Co can be divalent or trivalent. Therefore, in order to suppress the reduction of Co, it is preferable that the atmosphere in the heating furnace space 102 contains oxygen, more preferably the ratio of oxygen to nitrogen in the atmosphere in the heating furnace space 102 is equal to or higher than the air atmosphere, and further preferably the oxygen concentration in the atmosphere in the heating furnace space 102 is equal to or higher than the air atmosphere. Therefore, it is necessary to introduce an atmosphere containing oxygen into the heating furnace space.

[0058] A method of annealing while flowing oxygen gas from outside can be considered to introduce an atmosphere containing oxygen into the heating furnace space 102. However, the molecular weight of oxygen (O2) is about 32, and that of lithium fluoride (LiF) is about 26, so gaseous LiF is lighter than oxygen gas. Therefore, if annealing is performed while flowing oxygen gas, LiF vaporized by heating is likely to be discharged to the outside of the heating furnace space 102, and annealing in a LiF atmosphere may not be possible.

[0059] Therefore, in one embodiment of the present invention, as shown in Figures 3A and 3B, in order to perform annealing in an atmosphere containing fluoride, annealing is performed under either or both of the following conditions: no oxygen gas is flowed, or a lid 118 is placed on the container 116.

[0060] To perform annealing without flowing oxygen gas, a step of making the space 102 inside the heating furnace an oxygen-containing atmosphere and a step of placing the container 116 containing the mixture 903 in the space 102 inside the heating furnace are performed before heating. By performing the steps in this order, the mixture 903 can be annealed in an atmosphere containing oxygen and fluoride. During annealing, the space 102 inside the heating furnace is sealed to prevent the gas from being transported to the outside.

[0061] Alternatively, as shown in FIG. 3B, the container 116 is provided with a lid 118 for annealing. This configuration allows the space 119 closed by the container 116 and the lid 118 to be an atmosphere containing fluoride. Since the space 119 has a smaller volume than the space 102 in the heating furnace, a small amount of fluoride is vaporized, allowing the atmosphere to be made to contain fluoride. That is, the reaction system can be made to contain fluoride without significantly reducing the amount of fluoride contained in the mixture 903. Therefore, LiMO2 can be efficiently produced. In addition, the mixture 903 can be annealed in an atmosphere containing fluoride simply and inexpensively by using the lid 118.

[0062] By providing the lid 118, it is possible to perform annealing in an atmosphere containing a sufficient amount of fluoride without sealing the space 102 inside the heating furnace. Therefore, when the lid 118 is provided, annealing can be performed by flowing oxygen gas. In particular, it is preferable to provide the lid 118 on a deep container 116a as shown in Figures 3A and 3B. The deep container 116a has a relatively larger space 119a relative to the amount of mixture 903 when the mixture 903 is placed to the same depth than the shallow container 116. Therefore, an atmosphere containing a sufficient amount of fluoride can be maintained.

[0063] It is more preferable to perform annealing without flowing oxygen gas and with the lid 118 in place.

[0064] 4A and 4B show detailed steps in the case where oxygen gas is not flowed in step S34 shown in FIG. 1. There is no particular restriction on the order of the step of making the heating furnace space 102 into an oxygen-containing atmosphere (step S34-1 in FIG. 4A and FIG. 4B) and the step of placing the container 116 containing the mixture 903 in the heating furnace space 102 (step S34-2 in FIG. 4A and FIG. 4B). As shown in FIG. 4B, the step of making the heating furnace space 102 into an oxygen-containing atmosphere may be performed after placing the container 116 containing the mixture 903 in the heating furnace space 102. After performing these steps, the step of heating the heating furnace 120 (S34-3 in FIG. 4A and FIG. 4B) is performed.

[0065] There is no particular limitation on the method for making the space 102 inside the heating furnace into an oxygen-containing atmosphere, but one example is a method of evacuating the space 102 inside the heating furnace and then introducing a gas containing oxygen, such as oxygen gas or dry air, or a method of flowing in a gas containing oxygen, such as oxygen gas or dry air, for a certain period of time. Among these, it is preferable to evacuate the space 102 inside the heating furnace and then introduce oxygen gas (oxygen replacement). Note that air may be used as the oxygen-containing atmosphere.

[0066] The process of placing the container 116 containing the mixture 903 in the space inside the heating furnace 102 is not particularly limited, but examples thereof include a method of placing the container 116 directly in the space inside the heating furnace 102, and a method of using an apparatus having a conveying mechanism as shown in FIG. 5A and placing the container 116 in the space inside the heating furnace 102 by the conveying mechanism.

[0067] There is no particular limitation on the process for heating the heating furnace 120. Heating may be performed using a heating mechanism provided in the heating furnace 120.

[0068] Furthermore, there is no particular limitation on the arrangement of mixture 903 when placed in container 116, but it is preferable to arrange mixture 903 so that the upper surface of mixture 903 is flat with respect to the bottom surface of container 116, in other words, so that the height of the upper surface of mixture 903 is uniform, as shown in Figures 3A and 3B.

[0069] The annealing is preferably performed at an appropriate temperature and time. The appropriate temperature and time vary depending on conditions such as the size and composition of the particles of the composite oxide having lithium, transition metal, and oxygen in step S25. If the particles are small, a lower temperature or a shorter time may be more preferable than if the particles are large.

[0070] For example, when the average particle size (D50) of the particles in step S25 is about 12 μm, the annealing time is preferably, for example, 3 hours or more, and more preferably 10 hours or more.

[0071] On the other hand, when the average particle size (D50) of the particles in step S25 is about 5 μm, the annealing time is preferably, for example, from 1 hour to 10 hours, and more preferably about 2 hours.

[0072] The temperature drop time after annealing is preferably, for example, 10 hours or more and 50 hours or less.

[0073] The annealed material is collected (Step S35 in FIG. 1), and positive electrode active material 904 is obtained (Step S36 in FIG. 1).

[0074] An example of a heating furnace is shown in Figure 5. In Figure 5, parts having the same functions as those shown in Figure 3 are given the same hatch pattern, and the reference numerals may be omitted. Also, parts having the same functions are given the same reference numerals, and detailed descriptions thereof may be omitted.

[0075] <Heating furnace configuration> The heating furnace used in one embodiment of the present invention is not particularly limited, and various heating furnaces such as batch type and continuous type heating furnaces can be used, examples of which are shown in Figures 5A and 5B.

[0076] The heating furnace 130 shown in FIG. 5A is an example of a continuous heating furnace. The heating furnace 130 has a belt conveyor 132. By disposing a container 134 containing a mixture 903 on the belt conveyor 132 and treating the mixture in the heating furnace 130, it is possible to perform annealing continuously. The annealing time can be adjusted by adjusting the moving speed of the belt conveyor. In addition, by disposing a fluoride 906 in one of the containers 134 and annealing it simultaneously with the mixture 903, it is possible to make the space 102 inside the heating furnace a fluoride atmosphere. It is preferable to cover the container 134 as in FIG. 3B. By annealing the mixture 903 in the heating furnace 130, a positive electrode active material 904 can be obtained.

[0077] The heating furnace 140 shown in FIG. 5B is an example of a rotary heating furnace. The heating furnace 140 has a material input section 142, an atmosphere control section 144, and a recovery section 146. The mixture 903 is input from the material input section 142 into the space 102 inside the heating furnace. The heating plate 104 has a mechanism for rotating, and the heating plate 104 is further tilted toward the recovery section 146. With this configuration, the mixture 903 can be annealed while being made to flow. The annealing time can be adjusted by adjusting the tilt and the rotation speed. The annealed mixture 903 is recovered in the recovery section 146, and the positive electrode active material 904 can be obtained.

[0078] Moreover, the oxygen atmosphere and the fluoride atmosphere in the heating furnace space 102 can be adjusted by the atmosphere control unit 144 .

[0079] This embodiment mode can be implemented in appropriate combination with other embodiment modes.

[0080] (Embodiment 2) An example of a method for producing LiMO2 will be described below. Below, a production method in which a plurality of metal elements are further used as the metal element other than Co contained in LiMO2 will be described with reference to FIG.

[0081] <Preparation method 2 of positive electrode active material> FIG. 6 shows an example of a manufacturing process of a composite oxide containing Mg, Ni, and Al in addition to Co as LiMO2. In this manufacturing method, each metal element source other than Li and Co is mixed and pulverized separately, and then each metal element source that has been pulverized is mixed with lithium cobalt oxide and annealed. S11 to S36 are the same as the processes described in the first embodiment and FIG. 1. That is, in the step S34, it is preferable to anneal the mixture 903-2 in an atmosphere containing LiF. A positive electrode active material 904-2 is obtained by the manufacturing process shown in FIG. 6.

[0082] <Steps S15, S16, and S17> In addition, finely divided nickel hydroxide (Ni(OH)2) is prepared for mixing in step S31. The finely divided nickel hydroxide is previously subjected to step S15 in which nickel hydroxide is mixed with acetone and step S16 in which the nickel hydroxide is collected. By step S16, finely divided nickel hydroxide is obtained (step S17).

[0083] <Steps S18, S19, and S20> Also, finely divided aluminum hydroxide (Al(OH)3) is prepared for mixing in step S31. The finely divided aluminum hydroxide is previously subjected to step S18 in which the aluminum hydroxide is mixed with acetone and step S19 in which the aluminum hydroxide is collected. Finely divided aluminum hydroxide is obtained by step S19 (step S20).

[0084] In the above steps S15 to S20, nickel hydroxide is used as the nickel (Ni) source and aluminum hydroxide is used as the aluminum (Al) source, but the nickel source and aluminum source are not limited to these. Oxides and halides containing each element can also be used.

[0085] <Method 3 for preparing positive electrode active material> FIG. 7 shows an example of a process for producing a composite oxide containing Mg, Ni, and Al in addition to Co as LiMO2. In this production method, each metal element source other than Li and Co is mixed at the same time (S21), crushed, mixed with lithium cobalt oxide, and annealed. S31 to S35 are the same as the processes described in the first embodiment and FIG. 1. That is, in the step S34, it is preferable to anneal the mixture 903-3 in an atmosphere containing LiF. A positive electrode active material 904-3 can be obtained by the production process shown in FIG. 7.

[0086] <Steps S22 to S24> As in steps S15 to S17 and steps S18 to S20 described above, finely powdered MgF2, Ni(OH)2, and Al(OH)3 are prepared. The finely powdered aluminum hydroxide is previously subjected to step S22 in which the aluminum hydroxide is mixed with acetone and step S23 in which the aluminum hydroxide is collected. By step S22, a finely powdered mixture 902-3 is obtained (step S24).

[0087] <<Method 4 for preparing positive electrode active material>> FIG. 8 shows an example of a process for producing a composite oxide containing Mg, Ni, and Al in addition to Co as LiMO2. In this production method, a composite oxide represented by LiMO2 containing Mg is produced, and then a Ni source and an Al source are added to produce a composite oxide containing Mg, Ni, and Al. S11 to S14 and S31 to S36 are the same as the processes described in the first embodiment and FIG. 1. That is, in the step of S34, it is preferable to anneal the mixture 903 in an atmosphere containing LiF. Also, steps S15 to S17 are as described with reference to FIG. 6. A positive electrode active material 904-4 is obtained by the production process shown in FIG. 8.

[0088] As shown in step S50, the positive electrode active material 904 and the pulverized nickel hydroxide are mixed. Then, the mixed material is collected (step S51). The pulverized nickel hydroxide is previously subjected to step S15 in which nickel hydroxide is mixed with acetone and step S16 in which the nickel hydroxide is collected. By step S16, pulverized nickel hydroxide is obtained (step S17).

[0089] The materials mixed in step S50 are collected in step S51 to obtain a mixture 908 (step S52 in FIG. 8).

[0090] Next, Al is added through steps S53 to S55. Al can be added by using a liquid phase method such as a sol-gel method, a solid phase method, a sputtering method, a deposition method, a CVD (chemical vapor deposition) method, a PLD (pulsed laser deposition) method, or the like.

[0091] As shown in Fig. 8, first, in step S52, a metal source is prepared. When the sol-gel method is applied, a solvent to be used in the sol-gel method is prepared. As the Al source, Al alkoxide, Al hydroxide, Al oxide, etc. can be used. The number of cobalt atoms in lithium cobalt oxide is 1, and the concentration of aluminum in the metal source should be 0.001 times or more and 0.02 times or less.

[0092] As an example, a sol-gel method is applied, and aluminum isopropoxide is used as the metal source and 2-propanol is used as the solvent.

[0093] Next, aluminum alkoxide is dissolved in 2-propanol, and the mixture 905 is further mixed (Step S53 in FIG. 8).

[0094] The required amount of metal alkoxide varies depending on the particle size of lithium cobalt oxide. For example, when aluminum isopropoxide is used, if the particle size (D50) of lithium cobalt oxide is about 20 μm, it is preferable to add aluminum isopropoxide so that the concentration of aluminum contained in the lithium cobalt oxide is 0.001 to 0.02 times the number of cobalt atoms contained in the lithium cobalt oxide.

[0095] Next, the mixture of the alcohol solution of the metal alkoxide and the lithium cobalt oxide particles is stirred in a moisture-containing atmosphere. Stirring can be performed, for example, with a magnetic stirrer. The stirring time may be long enough for the water in the atmosphere and the metal alkoxide to undergo hydrolysis and polycondensation reactions, and may be performed, for example, for 4 hours under conditions of 25°C and 90% RH (relative humidity). Stirring may also be performed in an atmosphere without humidity and temperature control, for example, in the air atmosphere in a draft chamber. In such cases, it is preferable to use a longer stirring time, for example, 12 hours or more at room temperature.

[0096] By reacting the metal alkoxide with moisture in the atmosphere, the sol-gel reaction can proceed more slowly than when liquid water is added. Also, by reacting the metal alkoxide with water at room temperature, the sol-gel reaction can proceed more slowly than when, for example, heating is performed at a temperature above the boiling point of the alcohol solvent. By proceeding with the sol-gel reaction slowly, a coating layer with a uniform thickness and good quality can be formed.

[0097] The precipitate is collected from the mixed solution after the above treatment (step S54 in FIG. 8). The collection method can be filtration, centrifugation, evaporation to dryness, or the like. The precipitate can be washed with the same alcohol as the solvent in which the metal alkoxide was dissolved. When evaporation to dryness is used, it is not necessary to separate the solvent and the precipitate in this step, and the precipitate can be collected, for example, in the drying process of the next step (step S54).

[0098] Next, the collected residue is dried to obtain a mixture 909 (Step S55 in FIG. 8). The drying process can be performed, for example, by vacuum or ventilation drying at 80° C. for 1 hour or more and 4 hours or less.

[0099] Next, the resulting mixture is heated (Step S56 in FIG. 8).

[0100] The heating time is preferably set to a holding time within the heating temperature range of 1 hour to 80 hours.

[0101] The heating temperature is less than 1000°C, preferably 700°C to 950°C, and more preferably about 850°C.

[0102] Moreover, the heating is preferably carried out in an atmosphere containing oxygen.

[0103] In this embodiment, the heating temperature is set to 850° C. and held for 2 hours, the temperature increase rate is set to 200° C. / h, and the oxygen flow rate is set to 10 L / min.

[0104] The heating temperature in step S56 is preferably lower than the heating temperature in step S34.

[0105] <Step S57, Step S58> Next, the cooled particles are collected (Step S57 in FIG. 8). Furthermore, it is preferable to sieve the particles. Through the above steps, the positive electrode active material 904-4 can be produced (Step S58 in FIG. 8).

[0106] This embodiment mode can be implemented in appropriate combination with other embodiment modes.

[0107] (Embodiment 3) In this embodiment, an example of a structure of a positive electrode active material manufactured by a manufacturing method of one embodiment of the present invention will be described.

[0108] [Positive electrode active material structure] Materials having a layered rock salt crystal structure such as lithium cobalt oxide (LiCoO₂) are known to have a high discharge capacity and be excellent as a positive electrode active material for secondary batteries. Examples of materials having a layered rock salt crystal structure include composite oxides represented by LiMO₂. One or more selected from Co or Ni are cited as an example of the element M. Further, in addition to one or more selected from Co and Ni as an example of the element M, one or more selected from Al and Mg are cited.

[0109] It is known that the Jahn-Teller effect in transition metal compounds varies in its strength depending on the number of electrons in the d orbitals of the transition metal.

[0110] In compounds having nickel, distortion may easily occur due to the Jahn-Teller effect. Therefore, when charging and discharging at a high voltage in LiNiO₂, there is a concern that the crystal structure may collapse due to the distortion. It is suggested that the influence of the Jahn-Teller effect is small in LiCoO₂, and it may be more excellent in resistance to charging and discharging at a high voltage, which is preferable.

[0111] The positive electrode active material will be described with reference to FIGS. 9 and 10. FIGS. 9 and 10 describe the case where cobalt is used as the transition metal included in the positive electrode active material.

[0112] The positive electrode active material produced in one aspect of the present invention can reduce the shift of the CoO₂ layer in repeated charging and discharging at a high voltage. Further, the volume change can be reduced. Therefore, the compound can achieve excellent cycle characteristics. In addition, the compound can have a stable crystal structure in a charged state at a high voltage. Therefore, when the compound maintains a charged state at a high voltage, a short circuit is less likely to occur. In such a case, since the safety is further improved, it is preferable. In particular, the compound represented by the chemical formula Li (1-x-y) Co (1-a-b) Ni (x+a) Mg (y+b) O₂ is preferable because the characteristics are good when 0 < x + a ≤ 0.015 and 0 < y + b ≤ 0.06.

[0113] In this compound, the change in crystal structure and the difference in volume between a fully discharged state and a high-voltage charged state are small when compared per the same number of transition metal atoms.

[0114] FIG. 9 shows the crystal structure of the positive electrode active material 904 before and after charging and discharging. The positive electrode active material 904 is a composite oxide containing lithium, cobalt, and oxygen. In addition to the above, it preferably contains magnesium. It also preferably contains a halogen such as fluorine or chlorine. It also preferably contains aluminum and nickel.

[0115] The crystal structure at a charge depth of 0 (discharged state) in FIG. 9 is the same as that in FIG. 10, R-3m (O3). On the other hand, when the positive electrode active material 904 is at a fully charged charge depth, it has a crystal structure different from the H1-3 type crystal structure. This structure is in the space group R-3m, and although it is not a spinel type crystal structure, ions of cobalt, magnesium, etc. occupy oxygen 6 coordination positions, and the arrangement of cations has a symmetry similar to that of the spinel type. Therefore, this structure is referred to as a pseudo-spinel type crystal structure in this specification. In the diagram of the pseudo-spinel type crystal structure shown in FIG. 9, lithium is omitted in order to explain the symmetry of the cobalt atom and the symmetry of the oxygen atom, but in reality, for example, 20 atomic % or less of lithium is present between the CoO2 layers with respect to cobalt. In both the O3 type crystal structure and the pseudo-spinel type crystal structure, magnesium is preferably present dilutely between the CoO2 layers, that is, at the lithium site. In addition, halogen such as fluorine may be present randomly and dilutely at the oxygen site.

[0116] In addition, in the pseudospinel crystal structure, light elements such as lithium may occupy the oxygen tetracoordination site, and in this case too, the arrangement of ions has a symmetry similar to that of the spinel type.

[0117] It can also be said that the pseudo-spinel type crystal structure is a crystal structure similar to the CdCl2 type crystal structure, although it has random Li between the layers. This CdCl2 type-like crystal structure was observed when lithium nickel oxide was charged to a charge depth of 0.94 (Li 0.06 The crystal structure is close to that of lithium cobalt oxide (NiO2), but it is known that pure lithium cobalt oxide or layered rock salt type positive electrode active materials that contain a large amount of cobalt do not usually have this crystal structure.

[0118] The layered rock salt crystal and the anions of the rock salt crystal have a cubic close-packed structure (face-centered cubic lattice structure). It is presumed that the anions of the pseudo-spinel crystal also have a cubic close-packed structure. When they contact, there is a crystal plane where the orientation of the cubic close-packed structure formed by the anions is aligned. However, the space group of the layered rock salt crystal and the pseudo-spinel crystal is R-3m, which is different from the space group Fm-3m (the space group of a general rock salt crystal) and Fd-3m (the space group of a rock salt crystal with the simplest symmetry) of the rock salt crystal, so the Miller indices of the crystal planes that satisfy the above conditions are different between the layered rock salt crystal and the pseudo-spinel crystal and the rock salt crystal. In this specification, when the orientation of the cubic close-packed structure formed by the anions is aligned in the layered rock salt crystal, the pseudo-spinel crystal, and the rock salt crystal, it may be said that the crystal orientation is approximately the same.

[0119] In the positive electrode active material 904, the change in the crystal structure when a large amount of lithium is released by charging at a high voltage is suppressed more than in the positive electrode active material 100C described later. For example, as shown by the dotted line in FIG. 9, there is almost no displacement of the CoO2 layer in these crystal structures.

[0120] More specifically, the positive electrode active material 904 has a high structural stability even when the charging voltage is high. For example, in the positive electrode active material 100C, there is a charging voltage region where the R-3m(O3) crystal structure can be maintained even at a charging voltage that results in an H1-3 crystal structure, for example, a voltage of about 4.6V based on the potential of lithium metal, and there is a region where the pseudo-spinel crystal structure can be maintained even at a higher charging voltage, for example, a voltage of about 4.65V to 4.7V based on the potential of lithium metal. When the charging voltage is further increased, the H1-3 crystal may finally be observed. In addition, when graphite is used as the negative electrode active material in a secondary battery, there is a charging voltage region where the R-3m(O3) crystal structure can be maintained even at a voltage of 4.3V to 4.5V, and there is a region where the pseudo-spinel crystal structure can be maintained even at a higher charging voltage, for example, a voltage of 4.35V to 4.55V based on the potential of lithium metal.

[0121] Therefore, in the positive electrode active material 904, the crystal structure is not easily broken even when charging and discharging are repeated at a high voltage.

[0122] In addition, the pseudospinel crystal structure can be expressed by the coordinates of cobalt and oxygen in the unit cell being Co(0,0,0.5), O(0,0,x), with 0.20≦x≦0.25.

[0123] Magnesium, which is present randomly and dilutely between the CoO2 layers, i.e., at the lithium sites, has the effect of suppressing the displacement of the CoO2 layers. Therefore, when magnesium is present between the CoO2 layers, it is easy to form a pseudo-spinel type crystal structure. Therefore, it is preferable that magnesium is distributed throughout the particles of the positive electrode active material 100A-1. In order to distribute magnesium throughout the particles, it is preferable to perform a heat treatment in the manufacturing process of the positive electrode active material 100A-1.

[0124] However, if the heat treatment temperature is too high, cation mixing occurs, increasing the possibility that magnesium will enter the cobalt site. If magnesium is present at the cobalt site, it will no longer be effective in maintaining the R-3m structure. Furthermore, if the heat treatment temperature is too high, there are concerns that it may have adverse effects such as reducing cobalt to a divalent state and evaporating lithium.

[0125] Therefore, it is preferable to add a halogen compound such as a fluorine compound to the lithium cobalt oxide before the heat treatment for distributing magnesium throughout the particles. The addition of the halogen compound lowers the melting point of the lithium cobalt oxide. Lowering the melting point makes it easier to distribute magnesium throughout the particles at a temperature where cation mixing is unlikely to occur. Furthermore, the presence of a fluorine compound is expected to improve corrosion resistance against hydrofluoric acid produced by decomposition of the electrolyte.

[0126] If the magnesium concentration is increased above a desired value, the effect of stabilizing the crystal structure may be reduced. This is believed to be because magnesium enters the cobalt site in addition to the lithium site. The number of magnesium atoms in the positive electrode active material produced according to one embodiment of the present invention is preferably 0.001 times or more and 0.1 times or less than the number of cobalt atoms, more preferably more than 0.01 times and less than 0.04 times, and even more preferably about 0.02 times. The magnesium concentration shown here may be, for example, a value obtained by performing elemental analysis of the entire particle of the positive electrode active material using ICP-MS or the like, or may be based on the value of the raw material composition in the process of producing the positive electrode active material.

[0127] The number of nickel atoms in the positive electrode active material 904 is preferably 7.5% or less of the number of cobalt atoms, more preferably 0.05% to 4%, and more preferably 0.1% to 2%. The nickel concentration shown here may be a value obtained by performing elemental analysis of the entire particles of the positive electrode active material using, for example, ICP-MS or the like, or may be based on the value of the composition of raw materials in the process of producing the positive electrode active material.

[0128] ≪Particle size≫ If the particle size of the positive electrode active material 904 is too large, problems arise such as difficulty in diffusing lithium, and the surface of the active material layer becomes too rough when applied to a current collector. On the other hand, if the particle size is too small, problems arise such as difficulty in supporting the active material layer when applied to a current collector, and excessive reaction with an electrolyte. For this reason, the average particle size (D50: also referred to as median diameter) is preferably 1 μm or more and 100 μm or less, more preferably 2 μm or more and 40 μm or less, and even more preferably 5 μm or more and 30 μm or less.

[0129] <Analysis method> Whether or not a certain positive electrode active material exhibits a pseudospinel crystal structure when charged at a high voltage can be determined by analyzing the positive electrode charged at a high voltage using XRD, electron beam diffraction, neutron beam diffraction, electron spin resonance (ESR), nuclear magnetic resonance (NMR), etc. In particular, XRD is preferable in that it can analyze the symmetry of transition metals such as cobalt contained in the positive electrode active material with high resolution, it can compare the degree of crystallinity and the orientation of the crystals, it can analyze the periodic distortion of the lattice and the crystallite size, and it can obtain sufficient accuracy even when the positive electrode obtained by disassembling the secondary battery is directly measured.

[0130] As described above, the positive electrode active material 904 is characterized by a small change in crystal structure between a high-voltage charged state and a discharged state. A material in which a crystal structure that changes greatly from a discharged state when charged at a high voltage accounts for 50 wt% or more is not preferable because it cannot withstand high-voltage charging and discharging. It is also important to note that the desired crystal structure may not be obtained by simply adding an impurity element. For example, even if lithium cobalt oxide containing magnesium and fluorine is common in that it is charged at a high voltage, there are cases in which the pseudo-spinel crystal structure accounts for 60 wt% or more and cases in which the H1-3 crystal structure accounts for 50 wt% or more. In addition, at a certain voltage, the pseudo-spinel crystal structure is almost 100 wt%, and when the certain voltage is further increased, the H1-3 crystal structure may occur. Therefore, it is preferable to analyze the crystal structure of the positive electrode active material 904 by XRD or the like.

[0131] However, when the positive electrode active material is charged or discharged at a high voltage, its crystal structure may change when it comes into contact with the air. For example, it may change from a pseudo-spinel crystal structure to an H1-3 crystal structure. Therefore, it is preferable to handle all samples in an inert atmosphere, such as an atmosphere containing argon.

[0132] <Comparative Positive Electrode Active Material 100C> The positive electrode active material 100C shown in Fig. 10 is lithium cobalt oxide (LiCoO2) to which no halogen or magnesium is added, which is prepared by a method to be described later. As described in Non-Patent Documents 1 and 2, etc., the crystal structure of the lithium cobalt oxide shown in Fig. 10 changes depending on the charge depth.

[0133] As shown in Figure 10, lithium cobalt oxide at a charge depth of 0 (discharged state) has a region with a crystal structure of space group R-3m, and there are three CoO2 layers in the unit cell. Therefore, this crystal structure is sometimes called an O3 type crystal structure. Note that a CoO2 layer is an octahedral structure in which cobalt is coordinated with six oxygen atoms, and the octahedral structure is continuous on a plane with edge sharing.

[0134] At a charge depth of 1, the crystal structure has the space group P-3m1, and there is one CoO2 layer in the unit cell. Therefore, this crystal structure is sometimes called the O1 type crystal structure.

[0135] Lithium cobalt oxide at a charge depth of about 0.88 has a crystal structure of space group R-3m. This structure can be said to be a structure in which a CoO2 structure such as P-3m1(O1) and a LiCoO2 structure such as R-3m(O3) are alternately stacked. Therefore, this crystal structure is sometimes called an H1-3 type crystal structure. In reality, the number of cobalt atoms per unit cell in the H1-3 type crystal structure is twice that of other structures. However, in Figure 10 and other parts of this specification, the c-axis of the H1-3 type crystal structure is shown as half the unit cell in order to make it easier to compare with other structures.

[0136] As an example, as described in Non-Patent Document 3, the coordinates of cobalt and oxygen in the unit cell of the H1-3 type crystal structure can be expressed as Co(0,0,0.42150±0.00016), O1(0,0,0.27671±0.00045), and O2(0,0,0.11535±0.00045). O1 and O2 are oxygen atoms. Thus, the H1-3 type crystal structure is expressed by a unit cell using one cobalt and two oxygens. On the other hand, as described later, the pseudospinel type crystal structure of one embodiment of the present invention is preferably expressed by a unit cell using one cobalt and one oxygen. This indicates that the symmetry of cobalt and oxygen is different in the case of the pseudospinel structure and the case of the H1-3 type structure, and the pseudospinel structure has a smaller change from the O3 structure than the H1-3 type structure. The unit cell that is more preferably used to represent the crystal structure of the positive electrode active material may be selected, for example, so that the goodness of fit (GOF) value is smaller in Rietveld analysis of XRD.

[0137] When lithium cobalt oxide is repeatedly charged at a high voltage of 4.6 V or higher based on the redox potential of lithium metal, or when it is repeatedly charged to a deep depth of charge of 0.8 or higher, and then discharged, it undergoes repeated changes in crystal structure (i.e., a non-equilibrium phase change) between the H1-3 crystal structure and the R-3m(O3) structure in the discharged state.

[0138] However, these two crystal structures have a large deviation in the CoO2 layer. As shown by the dotted line and arrow in Figure 10, in the H1-3 type crystal structure, the CoO2 layer is significantly deviated from R-3m(O3). Such a dynamic structural change can have a negative effect on the stability of the crystal structure.

[0139] Furthermore, the difference in volume is large: when compared per the same number of cobalt atoms, the difference in volume between the H1-3 crystal structure and the O3 crystal structure in the discharged state is more than 3.0%.

[0140] In addition, the H1-3 crystal structure, which has continuous CoO2 layers such as P-3m1(O1), is likely to be unstable.

[0141] As a result, the crystal structure of lithium cobalt oxide breaks down when it is repeatedly charged and discharged at high voltages. This break in the crystal structure causes a deterioration in cycle characteristics. This is thought to be because the break in the crystal structure reduces the number of sites where lithium can exist stably and makes it difficult to insert and remove lithium.

[0142] This embodiment mode can be implemented in appropriate combination with other embodiment modes.

[0143] (Embodiment 4) In this embodiment, an example of a material that can be used in a secondary battery including a positive electrode active material manufactured by a manufacturing method according to one embodiment of the present invention will be described. In this embodiment, a secondary battery in which a positive electrode, a negative electrode, and an electrolyte are wrapped in an exterior body will be described as an example.

[0144] [Positive electrode] The positive electrode has a positive electrode active material layer and a positive electrode current collector.

[0145] <Cathode active material layer> The positive electrode active material layer contains positive electrode active material particles and may also contain a conductive assistant and a binder.

[0146] As the positive electrode active material particles, a positive electrode active material produced by the production method of one embodiment of the present invention can be used.

[0147] The conductive assistant may be a carbon material, a metal material, a conductive ceramic material, or the like. A fibrous material may also be used as the conductive assistant. The content of the conductive assistant relative to the total amount of the active material layer is preferably 1 wt% to 10 wt%, more preferably 1 wt% to 5 wt%.

[0148] The conductive assistant can form an electrical conductive network in the electrode. The conductive assistant can maintain an electrical conductive path between the positive electrode active materials. By adding the conductive assistant to the active material layer, an active material layer having high electrical conductivity can be realized.

[0149] As the conductive assistant, for example, natural graphite, artificial graphite such as mesocarbon microbeads, carbon fiber, etc. can be used. As the carbon fiber, for example, mesophase pitch carbon fiber, isotropic pitch carbon fiber, etc. can be used. As the carbon fiber, carbon nanofiber, carbon nanotube, etc. can be used. Carbon nanotube can be produced by, for example, vapor phase growth method, etc. As the conductive assistant, for example, carbon material such as carbon black (acetylene black (AB) etc.), graphite (graphite) particles, graphene, fullerene, etc. can be used. As the conductive assistant, for example, metal powder or metal fiber such as copper, nickel, aluminum, silver, gold, etc., conductive ceramic material, etc. can be used.

[0150] In addition, a graphene compound may be used as the conductive assistant.

[0151] Graphene compounds may have excellent electrical properties, such as high electrical conductivity, and excellent physical properties, such as high flexibility and high mechanical strength. In addition, graphene compounds have a planar shape. Graphene compounds enable surface contact with low contact resistance. In addition, even if they are thin, they may have very high electrical conductivity, and a conductive path can be efficiently formed in the active material layer with a small amount. Therefore, by using a graphene compound as a conductive assistant, it is preferable to increase the contact area between the active material and the conductive assistant. In addition, it is preferable to reduce electrical resistance in some cases. Here, it is particularly preferable to use graphene, multi-graphene, or reduced graphene oxide (hereinafter, RGO) as the graphene compound. Here, RGO refers to a compound obtained by reducing graphene oxide (GO: Graphene Oxide), for example.

[0152] When using active material particles having a small particle size, for example, active material particles having a size of 1 μm or less, the specific surface area of ​​the active material particles is large, and more conductive paths connecting the active material particles are required. In such a case, it is particularly preferable to use a graphene compound that can efficiently form conductive paths even in a small amount.

[0153] As an example, a cross-sectional configuration example in which a graphene compound is used as a conductive assistant in the active material layer 200 will be described below.

[0154] FIG. 11A shows a vertical cross-sectional view of an active material layer 200. FIG. 11B is an enlarged view of a region surrounded by a dotted line in FIG. 11A. The active material layer 200 includes a granular positive electrode active material 101, a graphene compound 201 as a conductive assistant, and a binder (not shown). Here, for example, graphene or multi-graphene may be used as the graphene compound 201. Here, the graphene compound 201 preferably has a sheet-like shape. Furthermore, the graphene compound 201 may be a sheet-like shape formed by partially overlapping a plurality of multi-graphenes or (and) a plurality of graphenes.

[0155] In the vertical cross section of the active material layer 200, as shown in Fig. 11A, sheet-like graphene compounds 201 are dispersed approximately uniformly inside the active material layer 200. In Fig. 11A, the graphene compounds 201 are typically represented by thick lines, but are actually thin films having a thickness corresponding to a single layer or multiple layers of carbon molecules. The multiple graphene compounds 201 are formed so as to wrap or cover the multiple granular positive electrode active materials 101 or to be attached to the surfaces of the multiple granular positive electrode active materials 101, and are therefore in surface contact with each other.

[0156] Here, a mesh-like graphene compound sheet (hereinafter referred to as a graphene compound net or graphene net) can be formed by bonding multiple graphene compounds together. When an active material is covered with a graphene net, the graphene net can also function as a binder that bonds the active materials together. Therefore, the amount of binder can be reduced or it is not necessary to use the binder, so that the ratio of the active material to the electrode volume or weight can be improved. In other words, the capacity of the power storage device can be increased.

[0157] Here, it is preferable to use graphene oxide as the graphene compound 201, mix it with an active material to form a layer that becomes the active material layer 200, and then reduce it. By using graphene oxide, which has extremely high dispersibility in a polar solvent, to form the graphene compound 201, it is possible to disperse the graphene compound 201 approximately uniformly inside the active material layer 200. Since the solvent is removed from the dispersion medium containing the uniformly dispersed graphene oxide and the graphene oxide is reduced, the graphene compound 201 remaining in the active material layer 200 is dispersed to such an extent that it partially overlaps with each other and is in surface contact with each other, thereby forming a three-dimensional conductive path. Note that the reduction of the graphene oxide may be performed by, for example, heat treatment or using a reducing agent.

[0158] Therefore, unlike a granular conductive assistant such as acetylene black that makes point contact with the active material, the graphene compound 201 enables surface contact with low contact resistance, and therefore the electrical conductivity between the granular positive electrode active material 101 and the graphene compound 201 can be improved with a smaller amount than that of a normal conductive assistant. Thus, the ratio of the positive electrode active material 101 in the active material layer 200 can be increased. This can increase the discharge capacity of the power storage device.

[0159] As the binder, it is preferable to use a rubber material such as styrene-butadiene rubber (SBR), styrene-isoprene-styrene rubber, acrylonitrile-butadiene rubber, butadiene rubber, ethylene-propylene-diene copolymer, etc. Also, as the binder, fluororubber can be used.

[0160] Moreover, it is preferable to use, for example, a water-soluble polymer as the binder. For example, polysaccharides can be used as the water-soluble polymer. For example, cellulose derivatives such as carboxymethyl cellulose (CMC), methyl cellulose, ethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, and regenerated cellulose, and starch can be used as the polysaccharide. It is even more preferable to use these water-soluble polymers in combination with the above-mentioned rubber material.

[0161] Alternatively, it is preferable to use materials such as polystyrene, polymethyl acrylate, polymethyl methacrylate (PMMA), sodium polyacrylate, polyvinyl alcohol (PVA), polyethylene oxide (PEO), polypropylene oxide, polyimide, polyvinyl chloride, polytetrafluoroethylene, polyethylene, polypropylene, polyisobutylene, polyethylene terephthalate, nylon, polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), ethylene propylene diene polymer, polyvinyl acetate, and nitrocellulose as the binder.

[0162] The binder may be used in combination of two or more of the above.

[0163] For example, a material having a particularly excellent viscosity adjusting effect may be used in combination with another material. For example, while rubber materials and the like have excellent adhesive strength and elasticity, it may be difficult to adjust the viscosity when mixed with a solvent. In such a case, it is preferable to mix the material with a material having a particularly excellent viscosity adjusting effect. For example, a water-soluble polymer may be used as a material having a particularly excellent viscosity adjusting effect. In addition, as a water-soluble polymer having a particularly excellent viscosity adjusting effect, the above-mentioned polysaccharides, for example, carboxymethylcellulose (CMC), methylcellulose, ethylcellulose, hydroxypropylcellulose, diacetylcellulose, cellulose derivatives such as regenerated cellulose, and starch may be used.

[0164] In addition, the solubility of cellulose derivatives such as carboxymethylcellulose is increased by converting them into salts such as sodium salts and ammonium salts of carboxymethylcellulose, and they are more likely to exhibit their effect as viscosity adjusters. The increased solubility can also increase the dispersibility of the active material and other components when preparing an electrode slurry. In this specification, the cellulose and cellulose derivatives used as electrode binders include their salts.

[0165] Water-soluble polymers stabilize the viscosity by dissolving in water, and can stably disperse active materials and other materials combined as binders, such as styrene-butadiene rubber, in an aqueous solution. In addition, since they have functional groups, they are expected to be easily and stably adsorbed onto the surface of active materials. In addition, many cellulose derivatives, such as carboxymethyl cellulose, have functional groups such as hydroxyl groups and carboxyl groups, and since they have functional groups, the polymers are expected to interact with each other and widely cover the surface of the active material.

[0166] When the binder covers the active material surface or contacts the surface to form a film, it is expected to function as a passive film and suppress the decomposition of the electrolyte. Here, the passive film is a film with no electrical conductivity or a film with extremely low electrical conductivity. For example, when a passive film is formed on the surface of the active material, it can suppress the decomposition of the electrolyte at the battery reaction potential. Moreover, it is more preferable that the passive film suppresses electrical conductivity and can conduct lithium ions.

[0167] <Positive electrode current collector> The positive electrode current collector may be made of a material having high electrical conductivity, such as metals such as stainless steel, gold, platinum, aluminum, and titanium, and alloys thereof. The material used for the positive electrode current collector is preferably one that does not dissolve at the potential of the positive electrode. Aluminum alloys to which elements that improve heat resistance, such as silicon, titanium, neodymium, scandium, and molybdenum, are added may be used. The positive electrode current collector may be made of a metal element that reacts with silicon to form silicide. Examples of metal elements that react with silicon to form silicide include zirconium, titanium, hafnium, vanadium, niobium, tantalum, chromium, molybdenum, tungsten, cobalt, and nickel. The current collector may be in the form of a foil, plate (sheet), net, punched metal, or expanded metal. The current collector may be made of a material having a thickness of 5 μm to 30 μm.

[0168] [Negative electrode] The negative electrode includes a negative electrode active material layer and a negative electrode current collector. The negative electrode active material layer may include a conductive assistant and a binder.

[0169] <Negative electrode active material> As the negative electrode active material, for example, an alloy-based material or a carbon-based material can be used.

[0170] As the negative electrode active material, an element capable of carrying out a charge / discharge reaction by alloying / dealloying reaction with lithium can be used. For example, a material containing at least one of silicon, tin, gallium, aluminum, germanium, lead, antimony, bismuth, silver, zinc, cadmium, indium, etc. can be used. Such elements have a larger capacity than carbon, and silicon in particular has a high theoretical capacity of 4200mAh / g. For this reason, it is preferable to use silicon as the negative electrode active material. Compounds containing these elements may also be used. For example, there are SiO, Mg2Si, Mg2Ge, SnO, SnO2, Mg2Sn, SnS2, V2Sn3, FeSn2, CoSn2, Ni3Sn2, Cu6Sn5, Ag3Sn, Ag3Sb, Ni2MnSb, CeSb3, LaSn3, La3Co2Sn7, CoSb3, InSb, SbSn, etc. Here, elements capable of undergoing charge / discharge reactions through alloying / dealloying reactions with lithium, and compounds containing such elements, are sometimes referred to as alloying materials.

[0171] In this specification, SiO refers to, for example, silicon monoxide. Alternatively, SiO x Here, x preferably has a value of 1 or close to 1. For example, x is preferably 0.2 or more and 1.5 or less, and more preferably 0.3 or more and 1.2 or less.

[0172] Examples of the carbon-based material that can be used include graphite, easily graphitizable carbon (soft carbon), non-graphitizable carbon (hard carbon), carbon nanotubes, graphene, and carbon black.

[0173] Examples of graphite include artificial graphite and natural graphite. Examples of artificial graphite include mesocarbon microbeads (MCMB), coke-based artificial graphite, and pitch-based artificial graphite. Here, as the artificial graphite, spherical graphite having a spherical shape can be used. For example, MCMB may have a spherical shape, which is preferable. In addition, it is relatively easy to reduce the surface area of ​​MCMB, which may be preferable. Examples of natural graphite include flake graphite and spheroidized natural graphite.

[0174] When lithium ions are inserted into graphite (when lithium-graphite intercalation compounds are formed), graphite exhibits a low potential similar to that of lithium metal (0.05 V to 0.3 V vs. Li / Li + ) This allows lithium-ion secondary batteries to exhibit high operating voltages. Furthermore, graphite is preferred because it has the advantages of relatively high capacity per unit volume, relatively small volume expansion, low cost, and high safety compared to lithium metal.

[0175] In addition, titanium dioxide (TiO2), lithium titanium oxide (Li4Ti5O 12 ), lithium-graphite intercalation compound (Li x C6), niobium pentoxide (Nb2O5), tungsten oxide (WO2), molybdenum oxide (MoO2), and other oxides can be used.

[0176] In addition, the negative electrode active material is Li3N-type Li, a complex nitride of lithium and transition metals. 3-x M x N (M=Co, Ni, Cu) can be used. For example, Li 2.6 Co 0.4 N3 has a large charge / discharge capacity (900mAh / g, 1890mAh / cm 3 ) and is preferred.

[0177] When a composite nitride of lithium and a transition metal is used, lithium ions are contained in the negative electrode active material, and therefore it is preferable to combine it with a material that does not contain lithium ions, such as V2O5 or Cr3O8, as the positive electrode active material. Even when a material that contains lithium ions is used as the positive electrode active material, the composite nitride of lithium and a transition metal can be used as the negative electrode active material by first removing the lithium ions contained in the positive electrode active material.

[0178] In addition, materials that undergo a conversion reaction can also be used as the negative electrode active material. For example, transition metal oxides that do not form an alloy with lithium, such as cobalt oxide (CoO), nickel oxide (NiO), and iron oxide (FeO), can be used as the negative electrode active material. Further examples of materials that undergo a conversion reaction include oxides such as Fe2O3, CuO, Cu2O, RuO2, and Cr2O3, and CoS 0.89 Examples of such oxides include sulfides such as NiS and CuS, nitrides such as Zn3N2, Cu3N and Ge3N4, phosphides such as NiP2, FeP2 and CoP3, and fluorides such as FeF3 and BiF3.

[0179] As the conductive assistant and binder that the negative electrode active material layer can have, the same materials as the conductive assistant and binder that the positive electrode active material layer can have can be used.

[0180] <Negative electrode current collector> The negative electrode current collector may be made of the same material as the positive electrode current collector, but it is preferable that the negative electrode current collector is made of a material that does not form an alloy with carrier ions such as lithium.

[0181] [Electrolyte] The electrolytic solution has a solvent and an electrolyte. The solvent of the electrolytic solution is preferably an aprotic organic solvent, and for example, one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate, chloroethylene carbonate, vinylene carbonate, γ-butyrolactone, γ-valerolactone, dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methyl formate, methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, 1,3-dioxane, 1,4-dioxane, dimethoxyethane (DME), dimethyl sulfoxide, diethyl ether, methyl diglyme, acetonitrile, benzonitrile, tetrahydrofuran, sulfolane, sultone, etc., or two or more of these can be used in any combination and ratio.

[0182] In addition, by using one or more ionic liquids (room-temperature molten salts) that are flame-retardant and non-volatile as a solvent for the electrolyte, even if the internal temperature of the electricity storage device rises due to an internal short circuit or overcharging, the electricity storage device can be prevented from bursting or catching fire. The ionic liquid is composed of a cation and an anion, and includes an organic cation and an anion. Examples of the organic cation used in the electrolyte include aliphatic onium cations such as quaternary ammonium cations, tertiary sulfonium cations, and quaternary phosphonium cations, and aromatic cations such as imidazolium cations and pyridinium cations. Examples of the anion used in the electrolyte include monovalent amide anions, monovalent methide anions, fluorosulfonic acid anions, perfluoroalkylsulfonic acid anions, tetrafluoroborate anions, perfluoroalkylborate anions, hexafluorophosphate anions, and perfluoroalkylphosphate anions.

[0183] Examples of the electrolyte to be dissolved in the above-mentioned solvent include LiPF6, LiClO4, LiAsF6, LiBF4, LiAlCl4, LiSCN, LiBr, LiI, Li2SO4, and Li2B 10 Cl 10 , Li2B 12 Cl 12 Lithium salts such as LiCF3SO3, LiC4F9SO3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiN(CF3SO2)2, LiN(C4F9SO2)(CF3SO2), LiN(C2F5SO2)2, etc. can be used alone or in any combination and ratio of two or more of these.

[0184] The electrolyte used in the electricity storage device is preferably a highly purified electrolyte with a low content of granular waste and elements other than the constituent elements of the electrolyte (hereinafter, simply referred to as "impurities"). Specifically, the weight ratio of impurities to the electrolyte is preferably 1% or less, more preferably 0.1% or less, and even more preferably 0.01% or less.

[0185] In addition, additives such as vinylene carbonate, propane sultone (PS), tert-butylbenzene (TBB), fluoroethylene carbonate (FEC), lithium bis(oxalate)borate (LiBOB), and dinitrile compounds such as succinonitrile and adiponitrile may be added to the electrolyte. The concentration of the additive may be, for example, 0.1 wt % to 5 wt % of the total solvent.

[0186] Alternatively, a polymer gel electrolyte may be used in which a polymer is swollen with an electrolytic solution.

[0187] The use of a polymer gel electrolyte improves safety against leakage, etc. Also, it is possible to make the secondary battery thinner and lighter.

[0188] Examples of the polymer to be gelled include silicone gel, acrylic gel, acrylonitrile gel, polyethylene oxide gel, polypropylene oxide gel, and fluorine-based polymer gel. For example, polymers having a polyalkylene oxide structure such as polyethylene oxide (PEO), PVDF, polyacrylonitrile, and copolymers containing these can be used. For example, PVDF-HFP, which is a copolymer of PVDF and hexafluoropropylene (HFP), can be used. The polymer to be formed may also have a porous shape.

[0189] In addition, instead of the electrolyte, a solid electrolyte containing inorganic materials such as sulfides or oxides, or a solid electrolyte containing polymeric materials such as PEO (polyethylene oxide) can be used. When using a solid electrolyte, the installation of a separator or spacer becomes unnecessary. In addition, since the entire battery can be solidified, there is no risk of leakage, and safety is dramatically improved.

[0190] Therefore, the positive electrode active material manufactured by the manufacturing method according to one embodiment of the present invention can be applied to an all-solid-state battery. By applying the positive electrode active material to an all-solid-state battery, an all-solid-state battery with high safety and excellent characteristics can be obtained.

[0191] This embodiment mode can be implemented in appropriate combination with other embodiment modes.

[0192] (Embodiment 5) In this embodiment, an example of a shape of a secondary battery having a positive electrode active material manufactured by the manufacturing method described in the previous embodiment will be described. The description of the previous embodiment can be referred to for the material used in the secondary battery described in this embodiment.

[0193] [Coin-type secondary battery] First, an example of a coin-type secondary battery will be described. Fig. 12A is an external view of a coin-type (single-layer flat) secondary battery, and Fig. 12B is a cross-sectional view thereof.

[0194] In the coin-type secondary battery 300, a positive electrode can 301, which also serves as a positive electrode terminal, and a negative electrode can 302, which also serves as a negative electrode terminal, are insulated and sealed with a gasket 303 made of polypropylene or the like. The positive electrode 304 is formed of a positive electrode current collector 305 and a positive electrode active material layer 306 provided in contact with the positive electrode current collector. The negative electrode 307 is formed of a negative electrode current collector 308 and a negative electrode active material layer 309 provided in contact with the negative electrode current collector.

[0195] In addition, the positive electrode 304 and the negative electrode 307 used in the coin-type secondary battery 300 each need only have an active material layer formed on one side.

[0196] Metals such as nickel, aluminum, and titanium that are corrosion-resistant to the electrolyte, or alloys of these metals and other metals (e.g., stainless steel, etc.) can be used for the positive electrode can 301 and the negative electrode can 302. In order to prevent corrosion by the electrolyte, it is preferable to coat them with nickel, aluminum, etc. The positive electrode can 301 is electrically connected to the positive electrode 304, and the negative electrode can 302 is electrically connected to the negative electrode 307.

[0197] These negative electrode 307, positive electrode 304, and separator 310 are impregnated with an electrolyte, and as shown in FIG. 12B, positive electrode can 301 is placed at the bottom, and positive electrode can 301 and negative electrode can 302 are laminated in this order, and positive electrode can 301 and negative electrode can 302 are crimped together via gasket 303, to produce coin-type secondary battery 300.

[0198] By using the positive electrode active material particles described in the above embodiment for the positive electrode 304, the coin-type secondary battery 300 can be made less susceptible to deterioration and highly safe.

[0199] [Separator] The secondary battery preferably has a separator. The separator may be made of, for example, paper or other cellulose-containing fibers, nonwoven fabric, glass fiber, ceramics, or synthetic fibers using nylon (polyamide), vinylon (polyvinyl alcohol-based fibers), polyester, acrylic, polyolefin, or polyurethane. The separator is preferably processed into a bag shape and disposed so as to encase either the positive electrode or the negative electrode.

[0200] The separator may have a multi-layer structure. For example, an organic material film such as polypropylene or polyethylene may be coated with a ceramic material, a fluorine material, a polyamide material, or a mixture of these. As the ceramic material, for example, aluminum oxide particles or silicon oxide particles may be used. As the fluorine material, for example, PVDF or polytetrafluoroethylene may be used. As the polyamide material, for example, nylon or aramid (meta-aramid or para-aramid) may be used.

[0201] Coating with ceramic materials improves oxidation resistance, suppressing the deterioration of the separator during high-voltage charging and discharging, and improving the reliability of the secondary battery. Coating with fluorine-based materials also improves adhesion between the separator and electrodes, improving output characteristics. Coating with polyamide-based materials, especially aramid, improves heat resistance, improving the safety of the secondary battery.

[0202] For example, both sides of a polypropylene film may be coated with a mixture of aluminum oxide and aramid.Alternatively, the surface of the polypropylene film that contacts the positive electrode may be coated with a mixture of aluminum oxide and aramid, and the surface that contacts the negative electrode may be coated with a fluorine-based material.

[0203] By using a separator with a multi-layer structure, the safety of the secondary battery can be maintained even if the overall thickness of the separator is thin, and therefore the capacity per volume of the secondary battery can be increased.

[0204] [Cylindrical secondary battery] An example of a cylindrical secondary battery will be described with reference to Figures 13A to 13D. As shown in Figures 13A and 13B, a cylindrical secondary battery 600 has a positive electrode cap (battery lid) 601 on the top surface, and a battery can (external can) 602 on the side and bottom surfaces. The positive electrode cap and battery can (external can) 602 are insulated by a gasket (insulating packing) 610.

[0205] FIG. 13B is a schematic diagram showing a cross section of a cylindrical secondary battery. Inside a hollow cylindrical battery can 602, a battery element is provided in which a strip-shaped positive electrode 604 and a negative electrode 606 are wound with a separator 605 sandwiched therebetween. Although not shown, the battery element is wound around a center pin. One end of the battery can 602 is closed and the other end is open. For the battery can 602, metals such as nickel, aluminum, and titanium that are resistant to corrosion by the electrolyte, or alloys of these metals and other metals (e.g., stainless steel, etc.) can be used. In addition, it is preferable to coat the battery can 602 with nickel, aluminum, or the like to prevent corrosion by the electrolyte. Inside the battery can 602, the battery element in which the positive electrode, negative electrode, and separator are wound is sandwiched between a pair of opposing insulating plates 608 and 609. In addition, a nonaqueous electrolyte (not shown) is injected into the inside of the battery can 602 in which the battery element is provided. The non-aqueous electrolyte may be the same as that used in a coin-type secondary battery.

[0206] Since the positive and negative electrodes used in a cylindrical secondary battery are wound, it is preferable to form an active material on both sides of the current collector. A positive electrode terminal (positive electrode current collector lead) 603 is connected to the positive electrode 604, and a negative electrode terminal (negative electrode current collector lead) 607 is connected to the negative electrode 606. Both the positive electrode terminal 603 and the negative electrode terminal 607 can be made of a metal material such as aluminum. The positive electrode terminal 603 is resistance-welded to a safety valve mechanism 612, and the negative electrode terminal 607 is resistance-welded to the bottom of the battery can 602. The safety valve mechanism 612 is electrically connected to the positive electrode cap 601 via a PTC element (Positive Temperature Coefficient) 611. The safety valve mechanism 612 cuts off the electrical connection between the positive electrode cap 601 and the positive electrode 604 when the rise in the internal pressure of the battery exceeds a predetermined threshold value. The PTC element 611 is a thermosensitive resistor whose resistance increases when the temperature rises, and the increase in resistance limits the amount of current to prevent abnormal heat generation. Barium titanate (BaTiO3)-based semiconductor ceramics can be used for the PTC element.

[0207] 13C, a plurality of secondary batteries 600 may be sandwiched between conductive plates 613 and 614 to form a module 615. The plurality of secondary batteries 600 may be connected in parallel, in series, or in parallel and then further in series. By forming a module 615 having a plurality of secondary batteries 600, a large amount of power can be extracted.

[0208] FIG. 13D is a top view of the module 615. To clarify the drawing, the conductive plate 613 is shown with a dotted line. As shown in FIG. 13D, the module 615 may have a conductor 616 that electrically connects the multiple secondary batteries 600. The conductive plate 613 can be provided by overlapping the conductor 616. Also, a temperature control device 617 may be provided between the multiple secondary batteries 600. When the secondary battery 600 is overheated, it can be cooled by the temperature control device 617, and when the secondary battery 600 is too cold, it can be heated by the temperature control device 617. Therefore, the performance of the module 615 is less affected by the outside air temperature.

[0209] By using the positive electrode active material manufactured by the manufacturing method described in the above embodiment for the positive electrode 604, the cylindrical secondary battery 600 which is less susceptible to deterioration and has high safety can be provided.

[0210] [Structural example of power storage device] Another structural example of the power storage device will be described with reference to FIGS.

[0211] 14A and 14B are diagrams showing the external appearance of a power storage device. The power storage device has a circuit board 900 and a secondary battery 913. A label 910 is attached to the secondary battery 913. Furthermore, as shown in FIG. 14B, the power storage device has a terminal 951, a terminal 952, an antenna 914, and an antenna 915.

[0212] The circuit board 900 has a terminal 911 and a circuit 912. The terminal 911 is connected to a terminal 951, a terminal 952, an antenna 914, an antenna 915, and the circuit 912. Note that a plurality of terminals 911 may be provided, and each of the plurality of terminals 911 may be a control signal input terminal, a power supply terminal, or the like.

[0213] The circuit 912 may be provided on the back surface of the circuit board 900. The antennas 914 and 915 are not limited to being coil-shaped, and may be, for example, wire-shaped or plate-shaped. In addition, antennas such as planar antennas, aperture antennas, traveling wave antennas, EH antennas, magnetic field antennas, and dielectric antennas may be used. Alternatively, the antennas 914 and 915 may be flat conductors. This flat conductor can function as one of the conductors for electric field coupling. In other words, the antennas 914 and 915 may function as one of the two conductors of the capacitor. This allows power to be exchanged not only by electromagnetic fields and magnetic fields, but also by electric fields.

[0214] The line width of the antenna 914 is preferably larger than the line width of the antenna 915. This allows the amount of power received by the antenna 914 to be increased.

[0215] The power storage device includes a layer 916 between the antenna 914 and the antenna 915 and the secondary battery 913. The layer 916 has a function of shielding, for example, an electromagnetic field generated by the secondary battery 913. The layer 916 can be formed using, for example, a magnetic material.

[0216] The structure of the power storage device is not limited to that shown in FIG.

[0217] For example, as shown in Fig. 15A and Fig. 15B, an antenna may be provided on each of a pair of opposing surfaces of the secondary battery 913 shown in Fig. 14A and Fig. 14B. Fig. 15A is an external view of the pair of surfaces as viewed from one side, and Fig. 15B is an external view of the pair of surfaces as viewed from the other side. Note that the description of the power storage device shown in Fig. 14A and Fig. 14B can be used as appropriate for the same parts as those of the power storage device shown in Fig. 14A and Fig. 14B.

[0218] 15A, an antenna 914 is provided on one of a pair of surfaces of a secondary battery 913 with a layer 916 sandwiched therebetween, and as shown in Fig. 15B, an antenna 915 is provided on the other of the pair of surfaces of the secondary battery 913 with a layer 917 sandwiched therebetween. The layer 917 has a function of shielding, for example, an electromagnetic field caused by the secondary battery 913. The layer 917 can be made of, for example, a magnetic material.

[0219] By using the above structure, the size of both antenna 914 and antenna 915 can be increased.

[0220] Alternatively, as shown in Fig. 15C and Fig. 15D, a separate antenna may be provided on each of a pair of opposing surfaces of the secondary battery 913 shown in Fig. 14A and Fig. 14B. Fig. 15C is an external view of the pair of surfaces as viewed from one side, and Fig. 15D is an external view of the pair of surfaces as viewed from the other side. Note that the description of the power storage device shown in Fig. 14A and Fig. 14B can be used as appropriate for the same parts as those of the power storage device shown in Fig. 14A and Fig. 14B.

[0221] As shown in Fig. 15C, antennas 914 and 915 are provided on one of a pair of surfaces of a secondary battery 913 with a layer 916 interposed therebetween, and as shown in Fig. 15D, antenna 918 is provided on the other of the pair of surfaces of the secondary battery 913 with a layer 917 interposed therebetween. The antenna 918 has a function of performing data communication with an external device, for example. For example, an antenna having a shape applicable to the antennas 914 and 915 can be applied to the antenna 918. As a communication method between the power storage device and another device via the antenna 918, a response method that can be used between the power storage device and another device, such as NFC, can be applied.

[0222] 16A, a display device 920 may be provided on the secondary battery 913 shown in FIGS. 14A and 14B. The display device 920 is electrically connected to a terminal 911 via a terminal 919. Note that the label 910 does not need to be provided on the portion where the display device 920 is provided. Note that the description of the power storage device shown in FIGS. 14A and 14B can be appropriately applied to the same portions as those of the power storage device shown in FIGS. 14A and 14B.

[0223] For example, an image indicating whether charging is in progress, an image indicating the amount of stored power, etc. may be displayed on the display device 920. For example, electronic paper, a liquid crystal display device, an electroluminescence (EL) display device, etc. can be used as the display device 920. For example, the use of electronic paper can reduce the power consumption of the display device 920.

[0224] 16B, a sensor 921 may be provided in the secondary battery 913 shown in Fig. 14A and 14B. The sensor 921 is electrically connected to a terminal 911 via a terminal 922. Note that the description of the power storage device shown in Fig. 14A and 14B can be appropriately applied to the same parts as those of the power storage device shown in Fig. 14A and 14B.

[0225] The sensor 921 may have a function of measuring, for example, displacement, position, speed, acceleration, angular speed, rotation speed, distance, light, liquid, magnetism, temperature, chemical substances, sound, time, hardness, electric field, current, voltage, power, radiation, flow rate, humidity, gradient, vibration, odor, or infrared ray. By providing the sensor 921, for example, data indicating the environment in which the power storage device is placed (such as temperature) can be detected and stored in the memory in the circuit 912.

[0226] Further, a structural example of the secondary battery 913 will be described with reference to FIGS.

[0227] A secondary battery 913 shown in FIG. 17A has a wound body 950 in which terminals 951 and 952 are provided inside a housing 930. The wound body 950 is impregnated with an electrolyte inside the housing 930. The terminal 952 contacts the housing 930, and the terminal 951 does not contact the housing 930 by using an insulating material or the like. Note that in FIG. 17A, the housing 930 is illustrated separately for convenience, but in reality, the wound body 950 is covered by the housing 930, and the terminals 951 and 952 extend outside the housing 930. The housing 930 can be made of a metal material (e.g., aluminum) or a resin material.

[0228] As shown in Fig. 17B, the housing 930 shown in Fig. 17A may be formed from a plurality of materials. For example, the secondary battery 913 shown in Fig. 17B has a housing 930a and a housing 930b bonded together, and a wound body 950 is provided in the area surrounded by the housings 930a and 930b.

[0229] The housing 930a can be made of an insulating material such as organic resin. In particular, by using a material such as organic resin on the surface on which the antenna is formed, it is possible to suppress shielding of the electric field by the secondary battery 913. Note that if the shielding of the electric field by the housing 930a is small, antennas such as antenna 914 and antenna 915 may be provided inside the housing 930a. The housing 930b can be made of, for example, a metal material.

[0230] 18 shows the structure of the wound body 950. The wound body 950 has a negative electrode 931, a positive electrode 932, and a separator 933. The wound body 950 is a wound body in which the negative electrode 931 and the positive electrode 932 are stacked on top of each other with the separator 933 in between, and the laminated sheet is wound. Note that the stack of the negative electrode 931, the positive electrode 932, and the separator 933 may be stacked a plurality of times.

[0231] 14 via one of the terminal 951 and the terminal 952. The positive electrode 932 is connected to the terminal 911 shown in FIG 14 via the other of the terminal 951 and the terminal 952.

[0232] By using the positive electrode active material particles described in the above embodiment for the positive electrode 932, the secondary battery 913 which is less susceptible to deterioration and has high safety can be provided.

[0233] [Laminated secondary battery] Next, examples of laminated secondary batteries will be described with reference to Fig. 19 to Fig. 24. If the laminated secondary battery has a flexible structure, and is mounted on an electronic device having at least a flexible portion, the secondary battery can be bent in accordance with the deformation of the electronic device.

[0234] A laminated secondary battery 980 will be described with reference to Fig. 19A to Fig. 19C. The laminated secondary battery 980 has a wound body 993 shown in Fig. 19A. The wound body 993 has a negative electrode 994, a positive electrode 995, and a separator 996. The wound body 993 is formed by stacking the negative electrode 994 and the positive electrode 995 with the separator 996 sandwiched therebetween, in the same manner as the wound body 950 described in Fig. 18, and winding the laminated sheet.

[0235] The number of layers of the negative electrode 994, the positive electrode 995, and the separator 996 may be appropriately designed according to the required capacity and element volume. The negative electrode 994 is connected to a negative electrode current collector (not shown) via one of the lead electrodes 997 and 998, and the positive electrode 995 is connected to a positive electrode current collector (not shown) via the other of the lead electrodes 997 and 998.

[0236] As shown in Fig. 19B, a film 981 serving as an exterior body and a film 982 having a recess are bonded together by thermocompression or the like to form a space, and the above-mentioned wound body 993 is stored in the space, thereby producing a secondary battery 980 as shown in Fig. 19C. The wound body 993 has lead electrodes 997 and 998, and is impregnated with an electrolyte solution between the film 981 and the film 982 having a recess.

[0237] For example, a metal material such as aluminum or a resin material can be used for the film 981 and the film 982 having the recesses. If a resin material is used as the material for the film 981 and the film 982 having the recesses, the film 981 and the film 982 having the recesses can be deformed when an external force is applied, and a secondary battery having flexibility can be produced.

[0238] Although an example in which two films are used is shown in FIG. 19B and FIG. 19C, a space may be formed by folding one film, and the above-mentioned wound body 993 may be housed in the space.

[0239] By using the positive electrode active material particles described in the above embodiment for the positive electrode 995, the secondary battery 980 can be made less susceptible to deterioration and highly safe.

[0240] In addition, although an example of a secondary battery 980 having a wound body in a space formed by a film that serves as an outer casing has been described in Figures 19A to 19C, the secondary battery may also have a plurality of rectangular positive electrodes, separators, and negative electrodes in a space formed by a film that serves as an outer casing, as shown in Figure 20, for example.

[0241] 20A includes a positive electrode 503 having a positive electrode current collector 501 and a positive electrode active material layer 502, a negative electrode 506 having a negative electrode current collector 504 and a negative electrode active material layer 505, a separator 507, an electrolyte 508, and an exterior body 509. The separator 507 is disposed between the positive electrode 503 and the negative electrode 506 provided in the exterior body 509. The interior of the exterior body 509 is filled with the electrolyte 508. The electrolyte solution described in Embodiment 2 can be used as the electrolyte solution 508.

[0242] 20A, the positive electrode current collector 501 and the negative electrode current collector 504 also serve as terminals for obtaining electrical contact with the outside. Therefore, the positive electrode current collector 501 and the negative electrode current collector 504 may be arranged so as to be partially exposed to the outside from the exterior body 509. Alternatively, the positive electrode current collector 501 and the negative electrode current collector 504 may not be exposed to the outside from the exterior body 509, but may be exposed to the outside by using a lead electrode and ultrasonically bonding the lead electrode to the positive electrode current collector 501 or the negative electrode current collector 504.

[0243] In the laminated secondary battery 500, the exterior body 509 may be a three-layer laminate film having a highly flexible thin metal film such as aluminum, stainless steel, copper, nickel, etc., provided on a film made of a material such as polyethylene, polypropylene, polycarbonate, ionomer, polyamide, etc., and further having an insulating synthetic resin film such as a polyamide-based resin, polyester-based resin, etc., provided on the thin metal film as the outer surface of the exterior body.

[0244] 20B shows an example of the cross-sectional structure of a laminated secondary battery 500. For simplicity, Fig. 20A shows an example formed of two current collectors, but in reality, the battery is formed of a plurality of electrode layers.

[0245] In FIG. 20B, the number of electrode layers is 16 as an example. Even if the number of electrode layers is 16, the secondary battery 500 has flexibility. FIG. 20B shows a structure of 16 layers in total, including 8 layers of negative electrode collector 504 and 8 layers of positive electrode collector 501. FIG. 20B shows a cross section of the negative electrode lead-out portion, in which 8 layers of negative electrode collector 504 are ultrasonically bonded. Of course, the number of electrode layers is not limited to 16, and may be more or less. When the number of electrode layers is large, a secondary battery having a larger capacity can be obtained. Also, when the number of electrode layers is small, a secondary battery that can be made thin and has excellent flexibility can be obtained.

[0246] 21 and 22 show an example of an external view of a laminated secondary battery 500. In FIGS. 21 and 22, a positive electrode 503, a negative electrode 506, a separator 507, an exterior body 509, a positive electrode lead electrode 510, and a negative electrode lead electrode 511 are provided.

[0247] FIG. 23A shows an external view of a positive electrode 503 and a negative electrode 506. The positive electrode 503 has a positive electrode current collector 501, and a positive electrode active material layer 502 is formed on the surface of the positive electrode current collector 501. The positive electrode 503 has a region where the positive electrode current collector 501 is partially exposed (hereinafter referred to as a tab region). The negative electrode 506 has a negative electrode current collector 504, and a negative electrode active material layer 505 is formed on the surface of the negative electrode current collector 504. The negative electrode 506 has a region where the negative electrode current collector 504 is partially exposed, that is, a tab region. The areas and shapes of the tab regions of the positive electrode and the negative electrode are not limited to the example shown in FIG. 23A.

[0248] [Method of manufacturing laminated secondary battery] Here, an example of a method for producing the laminate type secondary battery whose external view is shown in FIG. 21 will be described with reference to FIGS. 23B and 23C.

[0249] First, the negative electrode 506, the separator 507, and the positive electrode 503 are laminated. FIG. 23B shows the laminated negative electrode 506, the separator 507, and the positive electrode 503. Here, an example is shown in which five pairs of negative electrodes and four pairs of positive electrodes are used. Next, the tab regions of the positive electrodes 503 are joined together, and the positive electrode lead electrode 510 is joined to the tab region of the outermost positive electrode. For example, ultrasonic welding or the like may be used for the joining. Similarly, the tab regions of the negative electrodes 506 are joined together, and the negative electrode lead electrode 511 is joined to the tab region of the outermost negative electrode.

[0250] Next, the negative electrode 506 , the separator 507 and the positive electrode 503 are placed on the exterior body 509 .

[0251] Next, as shown in Fig. 23C, exterior body 509 is folded at the portion indicated by the dashed line. After that, the outer periphery of exterior body 509 is joined. For the joining, for example, thermocompression bonding or the like may be used. At this time, a region (hereinafter referred to as an inlet) that is not joined is provided in a part (or one side) of exterior body 509 so that electrolyte 508 can be introduced later.

[0252] Next, electrolytic solution 508 is introduced into the inside of exterior body 509 through an inlet provided in exterior body 509. The introduction of electrolytic solution 508 is preferably performed under a reduced pressure atmosphere or an inert atmosphere. Finally, the inlet is joined. In this manner, secondary battery 500, which is a laminated type secondary battery, can be produced.

[0253] By using the positive electrode active material particles described in the above embodiment for the positive electrode 503, the secondary battery 500 can be made less susceptible to deterioration and highly safe.

[0254] [Bendable secondary battery] Next, an example of a bendable secondary battery will be described with reference to FIGS.

[0255] FIG. 24A shows a schematic top view of a bendable battery 250. FIG. 24B, FIG. 24C, and FIG. 24D are schematic cross-sectional views taken along the lines C1-C2, C3-C4, and A1-A2 in FIG. 24A, respectively. The battery 250 has an exterior body 251, and a positive electrode 211a and a negative electrode 211b housed inside the exterior body 251. A lead 212a electrically connected to the positive electrode 211a and a lead 212b electrically connected to the negative electrode 211b extend outside the exterior body 251. In addition to the positive electrode 211a and the negative electrode 211b, an electrolyte (not shown) is enclosed in the area surrounded by the exterior body 251.

[0256] The positive electrode 211a and the negative electrode 211b of the battery 250 will be described with reference to Fig. 25. Fig. 25A is a perspective view illustrating the stacking order of the positive electrode 211a, the negative electrode 211b, and the separator 214. Fig. 25B is a perspective view showing the lead 212a and the lead 212b in addition to the positive electrode 211a and the negative electrode 211b.

[0257] 25A, battery 250 has a plurality of rectangular positive electrodes 211a, a plurality of rectangular negative electrodes 211b, and a plurality of separators 214. Positive electrode 211a and negative electrode 211b each have a protruding tab portion and a portion other than the tab. A positive electrode active material layer is formed on one surface of positive electrode 211a in the portion other than the tab, and a negative electrode active material layer is formed on one surface of negative electrode 211b in the portion other than the tab.

[0258] The positive electrode 211a and the negative electrode 211b are stacked so that the surfaces of the positive electrode 211a on which the positive electrode active material layer is not formed and the surfaces of the negative electrode 211b on which the negative electrode active material layer is not formed are in contact with each other.

[0259] Furthermore, a separator 214 is provided between the surface of the positive electrode 211a on which the positive electrode active material layer is formed and the surface of the negative electrode 211b on which the negative electrode active material layer is formed. In Fig. 25, the separator 214 is indicated by a dotted line for ease of viewing.

[0260] 25B, the multiple positive electrodes 211a and the lead 212a are electrically connected at a joint 215a, and the multiple negative electrodes 211b and the lead 212b are electrically connected at a joint 215b.

[0261] Next, exterior body 251 will be described with reference to FIGS. 24B, 24C, 24D, and 24E.

[0262] The exterior body 251 has a film-like shape and is folded in two to sandwich the positive electrode 211a and the negative electrode 211b. The exterior body 251 has a folded portion 261, a pair of sealing portions 262, and a sealing portion 263. The pair of sealing portions 262 are provided to sandwich the positive electrode 211a and the negative electrode 211b, and can also be called side seals. The sealing portion 263 has a portion overlapping the lead 212a and the lead 212b, and can also be called a top seal.

[0263] It is preferable that exterior body 251 has a corrugated shape in which ridge lines 271 and valley lines 272 are alternately arranged in the portions overlapping with positive electrode 211a and negative electrode 211b. In addition, it is preferable that seal portion 262 and seal portion 263 of exterior body 251 are flat.

[0264] Fig. 24B is a cross section taken at a portion overlapping with ridge line 271, and Fig. 24C is a cross section taken at a portion overlapping with valley line 272. Fig. 24B and Fig. 24C both correspond to widthwise cross sections of battery 250 and positive electrode 211a and negative electrode 211b.

[0265] Here, the distance between the end of the negative electrode 211b in the width direction, i.e., the end of the negative electrode 211b, and the seal portion 262 is defined as the distance La. When the battery 250 is deformed by bending or the like, the positive electrode 211a and the negative electrode 211b are deformed so as to be displaced from each other in the length direction, as described below. At that time, if the distance La is too short, the exterior body 251 may be strongly rubbed against the positive electrode 211a and the negative electrode 211b, and the exterior body 251 may be damaged. In particular, if the metal film of the exterior body 251 is exposed, the metal film may be corroded by the electrolyte. Therefore, it is preferable to set the distance La as long as possible. On the other hand, if the distance La is made too large, the volume of the battery 250 increases.

[0266] Moreover, it is preferable that the distance La between the negative electrode 211b and the seal portion 262 is increased as the total thickness of the laminated positive electrode 211a and negative electrode 211b increases.

[0267] More specifically, when the total thickness of the laminated positive electrode 211a and negative electrode 211b is taken as thickness t, the distance La is preferably 0.8 to 3.0 times, more preferably 0.9 to 2.5 times, and even more preferably 1.0 to 2.0 times, of the thickness t. By setting the distance La in this range, a compact battery with high reliability against bending can be realized.

[0268] Furthermore, when the distance between the pair of seal portions 262 is distance Lb, it is preferable to set distance Lb sufficiently larger than the width of positive electrode 211a and negative electrode 211b (here, width Wb of negative electrode 211b). As a result, even if positive electrode 211a and negative electrode 211b come into contact with exterior body 251 when battery 250 is repeatedly deformed, such as by bending, parts of positive electrode 211a and negative electrode 211b can be displaced in the width direction, so that rubbing between positive electrode 211a and negative electrode 211b and exterior body 251 can be effectively prevented.

[0269] For example, it is preferable that the difference between the distance Lb between the pair of seal portions 262 and the width Wb of the negative electrode 211b is 1.6 to 6.0 times, preferably 1.8 to 5.0 times, and more preferably 2.0 to 4.0 times the thickness t of the positive electrode 211a and the negative electrode 211b.

[0270] In other words, it is preferable that the distance Lb, the width Wb, and the thickness t satisfy the relationship of the following formula 1.

[0271]

number

[0272] Here, a satisfies the range of 0.8 to 3.0, preferably 0.9 to 2.5, and more preferably 1.0 to 2.0.

[0273] 24D is a cross section including lead 212a, and corresponds to a cross section in the longitudinal direction of battery 250, positive electrode 211a, and negative electrode 211b. As shown in FIG. 24D, it is preferable that a space 273 is provided between exterior body 251 and the longitudinal ends of positive electrode 211a and negative electrode 211b at bent portion 261.

[0274] Fig. 24E shows a schematic cross-sectional view of the bent battery 250. Fig. 24E corresponds to the cross section taken along the cutting line B1-B2 in Fig. 24A.

[0275] When the battery 250 is bent, a part of the exterior body 251 located on the outside of the bend is stretched, and another part located on the inside is deformed so as to contract. More specifically, the part located on the outside of the exterior body 251 is deformed so that the wave amplitude becomes smaller and the wave period becomes larger. On the other hand, the part located on the inside of the exterior body 251 is deformed so that the wave amplitude becomes larger and the wave period becomes smaller. In this way, the deformation of the exterior body 251 relieves the stress applied to the exterior body 251 due to bending, so that the material constituting the exterior body 251 itself does not need to expand or contract. As a result, the exterior body 251 is not damaged, and the battery 250 can be bent with a small force.

[0276] 24E, when the battery 250 is bent, the positive electrode 211a and the negative electrode 211b are displaced relative to each other. At this time, since one end of the multiple stacked positive electrodes 211a and negative electrodes 211b on the seal portion 263 side is fixed by the fixing member 217, the multiple stacked positive electrodes 211a and negative electrodes 211b are displaced such that the amount of displacement increases toward the bent portion 261. This relieves the stress applied to the positive electrodes 211a and negative electrodes 211b, and the positive electrodes 211a and negative electrodes 211b themselves do not need to expand or contract. As a result, the battery 250 can be bent without damaging the positive electrodes 211a and negative electrodes 211b.

[0277] Furthermore, by providing space 273 between positive electrode 211a and negative electrode 211b and exterior body 251, when bent, positive electrode 211a and negative electrode 211b located on the inside can shift relative to exterior body 251 without coming into contact with the exterior body 251.

[0278] 24 and 25 is a battery that is unlikely to suffer damage to the exterior body, the positive electrode 211a, the negative electrode 211b, etc., even when repeatedly bent and stretched, and the battery characteristics are unlikely to deteriorate. By using the positive electrode active material particles described in the previous embodiment for the positive electrode 211a of the battery 250, it is possible to obtain a secondary battery that is even less prone to deterioration and has a high level of safety.

[0279] This embodiment mode can be implemented in appropriate combination with other embodiment modes.

[0280] (Embodiment 6) In this embodiment, an example in which a secondary battery which is one embodiment of the present invention is mounted on an electronic device will be described.

[0281] First, an example of mounting the bendable secondary battery described in part of the fourth embodiment in an electronic device is shown in Fig. 26. Examples of electronic devices to which the bendable secondary battery is applied include television devices (also called televisions or television receivers), computer monitors, digital cameras, digital video cameras, digital photo frames, mobile phones (also called mobile phones or mobile phone devices), portable game machines, personal digital assistants, audio playback devices, and large game machines such as pachinko machines.

[0282] Furthermore, a secondary battery having a flexible shape can be incorporated into the inner or outer wall of a house or building, or along the curved surface of the interior or exterior of an automobile.

[0283] 26A shows an example of a mobile phone. The mobile phone 7400 includes a display unit 7402 built into a housing 7401, operation buttons 7403, an external connection port 7404, a speaker 7405, a microphone 7406, and the like. The mobile phone 7400 includes a secondary battery 7407.

[0284] FIG. 26B shows the mobile phone 7400 in a bent state. When the mobile phone 7400 is deformed by an external force and bent as a whole, the secondary battery 7407 provided inside is also bent. FIG. 26C shows the state of the bent secondary battery 7407 at that time. The secondary battery 7407 is a thin secondary battery. The secondary battery 7407 is fixed in a bent state. The secondary battery 7407 has a lead electrode electrically connected to a current collector.

[0285] FIG. 26D shows an example of a bangle-type display device. The portable display device 7100 includes a housing 7101, a display unit 7102, an operation button 7103, and a secondary battery 7104. FIG. 26E shows a bent state of the secondary battery 7104. When the secondary battery 7104 is bent and worn on the user's arm, the housing deforms and the curvature of part or all of the secondary battery 7104 changes. The degree of bending at any point of the curve expressed by the value of the radius of the corresponding circle is called the radius of curvature, and the reciprocal of the radius of curvature is called the curvature. Specifically, part or all of the main surface of the housing or the secondary battery 7104 changes within a range of the radius of curvature of 40 mm or more and 150 mm or less. If the radius of curvature of the main surface of the secondary battery 7104 is within a range of 40 mm or more and 150 mm or less, high reliability can be maintained.

[0286] 26F shows an example of a wristwatch-type portable information terminal 7200. A portable information terminal 7200 includes a housing 7201, a display portion 7202, a band 7203, a buckle 7204, operation buttons 7205, an input / output terminal 7206, and the like.

[0287] The portable information terminal 7200 can execute various applications such as mobile telephone, e-mail, document browsing and creation, music playback, Internet communication, and computer games.

[0288] The display surface of the display portion 7202 is curved, and display can be performed along the curved display surface. The display portion 7202 is also provided with a touch sensor, and can be operated by touching the screen with a finger, a stylus, or the like. For example, an application can be started by touching an icon 7207 displayed on the display portion 7202.

[0289] The operation button 7205 can have various functions, such as time setting, power on / off operation, wireless communication on / off operation, silent mode activation / cancellation, power saving mode activation / cancellation, etc. For example, the function of the operation button 7205 can be freely set by an operating system built into the mobile information terminal 7200.

[0290] The mobile information terminal 7200 can also perform short-distance wireless communication according to a communication standard. For example, the mobile information terminal 7200 can communicate with a wireless headset to enable hands-free calling.

[0291] The portable information terminal 7200 also includes an input / output terminal 7206, and can directly exchange data with other information terminals via a connector. Charging can also be performed via the input / output terminal 7206. Note that charging may be performed by wireless power supply without using the input / output terminal 7206.

[0292] The secondary battery of one embodiment of the present invention is included in the display portion 7202 of the portable information terminal 7200. For example, the secondary battery 7104 shown in FIG. 26E can be incorporated in a curved state inside the housing 7201 or in a bendable state inside the band 7203.

[0293] The portable information terminal 7200 preferably has a sensor. For example, it is preferable to mount a human body sensor such as a fingerprint sensor, a pulse sensor, or a body temperature sensor, a touch sensor, a pressure sensor, an acceleration sensor, or the like, as the sensor.

[0294] 26G illustrates an example of an armband-type display device. The display device 7300 includes a display portion 7304 and a secondary battery of one embodiment of the present invention. The display device 7300 can also include a touch sensor in the display portion 7304 and can function as a portable information terminal.

[0295] The display surface of the display portion 7304 is curved, and display can be performed along the curved display surface. In addition, the display device 7300 can change the display state by short-range wireless communication according to a communication standard.

[0296] The display device 7300 also includes an input / output terminal, and can directly exchange data with other information terminals via a connector. Charging can also be performed via the input / output terminal. Note that charging may be performed by wireless power supply without using the input / output terminal.

[0297] Next, an example of a tablet terminal that can be folded in two is shown in Fig. 27A and Fig. 27B. The tablet terminal 9600 shown in Fig. 27A and Fig. 27B has a housing 9630a, a housing 9630b, a movable part 9640 that connects the housings 9630a and 9630b, a display part 9631, a display mode changeover switch 9626, a power switch 9627, a power saving mode changeover switch 9625, a fastener 9629, and an operation switch 9628. By using a flexible panel for the display part 9631, a tablet terminal having a wider display part can be obtained. Fig. 27A shows the tablet terminal 9600 in an open state, and Fig. 27B shows the tablet terminal 9600 in a closed state.

[0298] The tablet terminal 9600 also includes a power storage unit 9635 inside the housing 9630a and the housing 9630b. The power storage unit 9635 passes through the movable portion 9640 and is provided across the housings 9630a and 9630b.

[0299] A part of the display portion 9631 can be a touch panel area, and data can be input by touching the displayed operation keys. Also, keyboard buttons can be displayed on the display portion 9631 by touching a position on the touch panel where a keyboard display switching button is displayed with a finger or a stylus.

[0300] Furthermore, the display mode changeover switch 9626 can change the display orientation, such as portrait or landscape, and can select black and white or color display. The power saving mode changeover switch 9625 can optimize the display brightness according to the amount of external light during use detected by an optical sensor built into the tablet terminal 9600. The tablet terminal may be equipped with not only an optical sensor, but also other detection devices such as a gyro, an acceleration sensor, or other sensors that detect tilt.

[0301] 27B shows a tablet terminal in a closed state, which includes a housing 9630, a solar cell 9633, and a charge / discharge control circuit 9634 including a DC-DC converter 9636. In addition, a secondary battery according to one embodiment of the present invention is used as a power storage unit 9635.

[0302] Note that the tablet terminal 9600 can be folded in two, and therefore can be folded so that the housing 9630a and the housing 9630b overlap each other when not in use. By folding, the display portion 9631 can be protected, and therefore durability of the tablet terminal 9600 can be improved. In addition, the power storage unit 9635 using the secondary battery of one embodiment of the present invention has a high capacity and favorable cycle characteristics, and therefore a tablet terminal that can be used for a long period of time can be provided.

[0303] In addition, the tablet terminal shown in Figures 27A and 27B can have a function to display various information (still images, videos, text images, etc.), a function to display a calendar, date or time on the display unit, a touch input function to operate or edit information displayed on the display unit by touch input, and a function to control processing by various software (programs), etc.

[0304] A solar cell 9633 attached to the surface of the tablet terminal can supply power to a touch panel, a display unit, a video signal processor, or the like. Note that the solar cell 9633 can be provided on one or both sides of the housing 9630, and a configuration can be adopted in which the power storage unit 9635 can be efficiently charged.

[0305] The configuration and operation of the charge / discharge control circuit 9634 shown in Fig. 27B are described with reference to a block diagram in Fig. 27C. Fig. 27C shows a solar cell 9633, a power storage unit 9635, a DCDC converter 9636, a converter 9637, switches SW1 to SW3, and a display unit 9631. The power storage unit 9635, the DCDC converter 9636, the converter 9637, and the switches SW1 to SW3 correspond to the charge / discharge control circuit 9634 shown in Fig. 27B.

[0306] First, an example of operation in the case where power is generated by the solar cell 9633 using external light will be described. The power generated by the solar cell is stepped up or stepped down by a DC-DC converter 9636 to a voltage for charging the power storage unit 9635. When power from the solar cell 9633 is used for the operation of the display unit 9631, a switch SW1 is turned on, and the converter 9637 steps up or steps down the voltage to a voltage required for the display unit 9631. When no display is to be performed on the display unit 9631, the switch SW1 is turned off and the switch SW2 is turned on to charge the power storage unit 9635.

[0307] Note that the solar cell 9633 is shown as an example of a power generating means, but is not particularly limited thereto, and may be configured to charge the power storage unit 9635 using other power generating means such as a piezoelectric element (piezo element) or a thermoelectric conversion element (Peltier element). For example, a non-contact power transmission module that transmits and receives power wirelessly (non-contact) for charging, or a combination with other charging means may be used.

[0308] FIG. 28 illustrates an example of another electronic device. In FIG. 28, a display device 8000 is an example of an electronic device using a secondary battery 8004 according to one embodiment of the present invention. Specifically, the display device 8000 corresponds to a display device for receiving a TV broadcast and includes a housing 8001, a display unit 8002, a speaker unit 8003, a secondary battery 8004, and the like. The secondary battery 8004 according to one embodiment of the present invention is provided inside the housing 8001. The display device 8000 can receive power from a commercial power source, and can also use power stored in the secondary battery 8004. Thus, even when power cannot be supplied from a commercial power source due to a power outage or the like, the display device 8000 can be used by using the secondary battery 8004 according to one embodiment of the present invention as an uninterruptible power source.

[0309] The display unit 8002 can be a liquid crystal display device, a light-emitting device having a light-emitting element such as an organic EL element in each pixel, an electrophoretic display device, a semiconductor display device such as a DMD (Digital Micromirror Device), a PDP (Plasma Display Panel), or an FED (Field Emission Display).

[0310] The display device includes all display devices for displaying information, such as display devices for receiving TV broadcasts, display devices for personal computers, display devices for advertisements, and the like.

[0311] 28, a stationary lighting device 8100 is an example of an electronic device using a secondary battery 8103 according to one embodiment of the present invention. Specifically, the lighting device 8100 includes a housing 8101, a light source 8102, a secondary battery 8103, and the like. FIG. 28 illustrates an example in which the secondary battery 8103 is provided inside a ceiling 8104 on which the housing 8101 and the light source 8102 are provided, but the secondary battery 8103 may be provided inside the housing 8101. The lighting device 8100 can receive power from a commercial power source or can use power stored in the secondary battery 8103. Thus, even when power cannot be supplied from a commercial power source due to a power outage or the like, the lighting device 8100 can be used by using the secondary battery 8103 according to one embodiment of the present invention as an uninterruptible power source.

[0312] Note that although Figure 28 illustrates an example of a stationary lighting device 8100 provided on a ceiling 8104, the secondary battery of one embodiment of the present invention can also be used in a stationary lighting device provided on a surface other than the ceiling 8104, such as a side wall 8105, a floor 8106, or a window 8107, or can also be used in a tabletop lighting device.

[0313] An artificial light source that artificially obtains light using electric power can be used as the light source 8102. Specifically, examples of the artificial light source include discharge lamps such as incandescent lamps and fluorescent lamps, and light-emitting elements such as LEDs and organic EL elements.

[0314] 28, an air conditioner including an indoor unit 8200 and an outdoor unit 8204 is an example of an electronic device using a secondary battery 8203 according to one embodiment of the present invention. Specifically, the indoor unit 8200 includes a housing 8201, an air outlet 8202, a secondary battery 8203, and the like. FIG. 28 illustrates an example in which the secondary battery 8203 is provided in the indoor unit 8200, but the secondary battery 8203 may be provided in the outdoor unit 8204. Alternatively, the secondary battery 8203 may be provided in both the indoor unit 8200 and the outdoor unit 8204. The air conditioner can receive power from a commercial power source or can use power stored in the secondary battery 8203. In particular, when a secondary battery 8203 is provided in both the indoor unit 8200 and the outdoor unit 8204, even when power cannot be supplied from a commercial power source due to a power outage or the like, the air conditioner can be used by using the secondary battery 8203 of one embodiment of the present invention as an uninterruptible power source.

[0315] Note that although FIG. 28 illustrates an example of a separate-type air conditioner including an indoor unit and an outdoor unit, a secondary battery according to one embodiment of the present invention can also be used in an integrated air conditioner that has the functions of an indoor unit and an outdoor unit in a single housing.

[0316] 28, an electric refrigerator-freezer 8300 is an example of an electronic device using a secondary battery 8304 according to one embodiment of the present invention. Specifically, the electric refrigerator-freezer 8300 includes a housing 8301, a refrigerator door 8302, a freezer door 8303, a secondary battery 8304, and the like. In FIG. 28, the secondary battery 8304 is provided inside the housing 8301. The electric refrigerator-freezer 8300 can receive power from a commercial power source or can use power stored in the secondary battery 8304. Thus, even when power cannot be supplied from the commercial power source due to a power outage or the like, the electric refrigerator-freezer 8300 can be used by using the secondary battery 8304 according to one embodiment of the present invention as an uninterruptible power source.

[0317] Also, by storing power in the secondary battery during time periods when electronic devices are not used, particularly during time periods when the ratio of the amount of power actually used to the total amount of power that can be supplied by the commercial power source (called the power usage rate) is low, it is possible to prevent the power usage rate from increasing outside of the above time periods. For example, in the case of an electric refrigerator-freezer 8300, power is stored in the secondary battery 8304 during the night when the temperature is low and the refrigerator door 8302 and the freezer door 8303 are not opened or closed. Then, during the daytime when the temperature is high and the refrigerator door 8302 and the freezer door 8303 are opened and closed, the secondary battery 8304 is used as an auxiliary power source, thereby making it possible to keep the daytime power usage rate low.

[0318] In addition to the electronic devices described above, the secondary battery of one embodiment of the present invention can be mounted on any electronic device. According to one embodiment of the present invention, a secondary battery with less deterioration and high safety can be obtained. Therefore, by mounting the secondary battery of one embodiment of the present invention on the electronic device described in this embodiment, the electronic device can have a longer life and a higher safety.

[0319] This embodiment mode can be implemented in appropriate combination with other embodiment modes.

[0320] (Embodiment 7) In this embodiment, an example in which a secondary battery according to one embodiment of the present invention is mounted on a vehicle will be described.

[0321] By installing a secondary battery in a vehicle, next-generation clean energy vehicles such as hybrid vehicles (HVs), electric vehicles (EVs), or plug-in hybrid vehicles (PHVs or PHEVs) can be realized.

[0322] FIG. 29 illustrates an example of a vehicle using a secondary battery according to one embodiment of the present invention. An automobile 8400 illustrated in FIG. 29A is an electric automobile using an electric motor as a power source for running. Alternatively, it is a hybrid automobile that can appropriately select and use an electric motor or an engine as a power source for running. By using the secondary battery according to one embodiment of the present invention, a vehicle with a long cruising distance can be realized. In addition, the automobile 8400 includes a secondary battery. The secondary battery not only drives the electric motor 8406, but can also supply power to a light-emitting device such as a headlight 8401 or a room light (not shown).

[0323] The secondary battery can also supply power to display devices such as a speedometer and a tachometer included in the automobile 8400. The secondary battery can also supply power to semiconductor devices such as a navigation system included in the automobile 8400.

[0324] The automobile 8500 shown in FIG. 29B can charge the secondary battery 8024 of the automobile 8500 by receiving power supply from an external charging facility by a plug-in method, a non-contact power supply method, or the like. FIG. 29B shows a state in which the secondary battery 8024 mounted on the automobile 8500 is being charged from a ground-mounted charging device 8021 via a cable 8022. When charging, the charging method and connector standards may be appropriately performed by a predetermined method such as CHAdeMO (registered trademark) or Combo. The charging device 8021 may be a charging station installed in a commercial facility, or may be a home power source. For example, the secondary battery 8024 mounted on the automobile 8500 can be charged by an external power supply using plug-in technology. Charging can be performed by converting AC power to DC power via a conversion device such as an ACDC converter.

[0325] Although not shown, a power receiving device may be mounted on a vehicle, and charging may be performed by supplying power contactlessly from a ground power transmitting device. In the case of this contactless power supply method, by incorporating a power transmitting device in a road or an exterior wall, charging may be performed not only while the vehicle is stopped but also while the vehicle is moving. This contactless power supply method may also be used to transmit and receive power between vehicles. Furthermore, a solar cell may be provided on the exterior of the vehicle, and a secondary battery may be charged while the vehicle is stopped or moving. For such contactless power supply, an electromagnetic induction method or a magnetic field resonance method may be used.

[0326] 29C is an example of a two-wheeled vehicle using the secondary battery of one embodiment of the present invention. A scooter 8600 shown in FIG. 29C includes a secondary battery 8602, a side mirror 8601, and a turn signal light 8603. The secondary battery 8602 can supply electricity to the turn signal light 8603.

[0327] 29C, the secondary battery 8602 can be stored in the under-seat storage 8604. The secondary battery 8602 can be stored in the under-seat storage 8604 even if the under-seat storage 8604 is small.

[0328] According to one embodiment of the present invention, a secondary battery with little deterioration and high safety can be obtained. Therefore, by mounting the secondary battery on a vehicle, it is possible to suppress a decrease in cruising distance, acceleration performance, and the like. In addition, a vehicle with high safety can be obtained. In addition, the secondary battery mounted on the vehicle can also be used as a power supply source other than the vehicle. In this case, for example, it is possible to avoid using a commercial power source during peak power demand. If it is possible to avoid using a commercial power source during peak power demand, it is possible to contribute to energy saving and reduction of carbon dioxide emissions. In addition, since the secondary battery with little deterioration and high safety can be used for a long period of time, it is possible to reduce the amount of rare metals used, including cobalt.

[0329] This embodiment mode can be implemented in appropriate combination with other embodiment modes. EXAMPLES

[0330] In this example, LiMO₂ prepared by the manufacturing method of one aspect of the present invention will be described. The manufacturing method will be described with reference to FIG. 1, FIG. 3B, and Table 2.

[0331] <Preparation of Each Sample of LiMO₂> First, a mixture 902 containing magnesium and fluorine was prepared (Steps S11 to S14). Lithium fluoride and magnesium fluoride were weighed so that the molar ratio of LiF:MgF₂ was 1:3, and acetone was added as a solvent for wet mixing and pulverization. The mixing and pulverization were performed using a ball mill with zirconia balls at 400 rpm for 12 hours. The processed material was recovered to obtain the mixture 902.

[0332] Next, lithium cobaltate was prepared as a composite oxide containing lithium and cobalt. More specifically, Celsid C-10N manufactured by Nippon Chemical Industry Co., Ltd. was prepared (Step S25).

[0333] Next, in Step S31, the mixture 902 was weighed so that the atomic weight of magnesium in the mixture 902 was 0.5 mol% with respect to the atomic weight of cobalt in lithium cobaltate. The mixing was performed dry using a ball mill with zirconia balls at 150 rpm for 1 hour. Then, it was recovered (Step S32) to obtain the mixture 903 (Step S33).

[0334] Next, the mixture 903 was placed in an alumina crucible (aluminum oxide crucible) and annealed in a muffle furnace (step S34). The annealing conditions varied depending on each sample and were as shown in Table 2. The temperature increase was set at 200 °C / h, and the temperature decrease was carried out over 10 hours or more. The material after the heat treatment was recovered and sieved (step S35) to obtain each sample (Comparative Sample 1, Comparative Sample 2, and Sample 3) (step S36). The actual alumina crucible used is shown in Fig. 30. Fig. 30A shows the state before covering the alumina crucible with a lid, and Fig. 30B shows the state when the alumina crucible was covered. As shown in Fig. 30B, Sample 3 was prepared with the alumina crucible covered.

[0335] Sample 3 was prepared by the production method of one aspect of the present invention. Comparative Sample 1 and Sample 3 differ in annealing time and O2 conditions. Comparative Sample 2 and Sample 3 differ in O2 conditions. Note that Comparative Sample 1 and Comparative Sample 2 were prepared under an O2 condition of "flow".

[0336]

Table 2

[0337] <Annealing method for each sample of LiMO2> Up to S33, it was the same for all samples. The annealing method in S34 differed depending on the sample. The conceptual diagram when annealing was carried out is as shown in Fig. 3B.

[0338] In Table 2, "sample weight" is the weight of the annealed mixture 903.

[0339] In Table 2, "annealing temperature" is the temperature when annealing was carried out, and "annealing time" is the time during which the annealing temperature was maintained.

[0340] In Table 2, "O2 conditions" refers to the method of introducing O2 into the space 102 inside the heating furnace, "flow" indicates that annealing was performed while introducing O2 at a flow rate of 10 L / min, and "purge" indicates that the space 102 inside the heating furnace was replaced with O2 before annealing, and then annealing was performed.

[0341] <Battery cell production> Next, the above-obtained comparative sample 1, comparative sample 2, and sample 3 were used as the positive electrode active material to fabricate each positive electrode. The positive electrode active material, AB, and PVDF were mixed in a ratio of active material:AB:PVDF=95:3:2 (weight ratio) and the slurry was applied to a current collector. NMP was used as the solvent for the slurry.

[0342] After the slurry was applied to the current collector, the solvent was evaporated. Then, pressure was applied at 210 kN / m, and then further pressure was applied at 1467 kN / m. A positive electrode was obtained by the above process. The amount of the positive electrode loaded was about 7 mg / cm. 2 The electrode density was set to >3.8g / cc.

[0343] Using the prepared positive electrode, a coin-type battery cell of the CR2032 type (diameter 20 mm, height 3.2 mm) was produced.

[0344] Lithium metal was used as the counter electrode.

[0345] The electrolyte used in the electrolytic solution was 1 mol / L lithium hexafluorophosphate (LiPF6), and the electrolytic solution was a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) at a volume ratio of EC:DEC = 3:7. For the secondary batteries used to evaluate the charge / discharge efficiency, 2 wt% vinylene carbonate (VC) was added to the electrolytic solution.

[0346] The separator was made of polypropylene having a thickness of 25 μm.

[0347] The positive electrode can and the negative electrode can were made of stainless steel (SUS).

[0348] <Measurement of Charge and Discharge Efficiency> The cycle characteristics of the battery cells fabricated using the obtained Comparative Sample 1, Comparative Sample 2, and Sample 3 were measured. The cycle characteristics were evaluated at 25°C with charging being CCCV (1.0C, 4.6V, termination current 0.1C) and discharging being CC (1.0C, 2.5V). The results are shown in Figure 31.

[0349] From Figure 31, it was found that Sample 3 fabricated according to one aspect of the present invention exhibited better cycle characteristics than Comparative Sample 2. Also, Sample 3 exhibited cycle characteristics equivalent to those of Comparative Sample 1. However, from Table 2, it can be seen that Sample 3 can fabricate the positive electrode active material with an annealing time that is 1 / 3 that of Comparative Sample 1. Therefore, it can be said that Sample 3 can fabricate a positive electrode active material with good characteristics in a short time. From the above, it was found that according to one aspect of the present invention, a positive electrode active material showing good characteristics can be fabricated in a short time. Also, it was found that Sample 3 can process a relatively large mass of 30 g at once. Therefore, it was found that according to one aspect of the present invention, a large amount of positive electrode active material having good characteristics can be fabricated in a short time.

Example

[0350] In this example, LiMO2 fabricated by a fabrication method of one aspect of the present invention different from that of Example 1 will be described. The fabrication method will be described with reference to Figure 1, Figure 3B, and Table 3.

[0351] <Fabrication of Each Sample of LiMO2> The mixture 902 was fabricated through steps S11 to S14 of Figure 1. It was carried out in the same manner as in Example 1 except that mixing and pulverization were performed dry. Subsequently, the cell seed C-10N and the mixture 902 were mixed in the same manner as steps S31 to S33 of Example 1 to obtain the mixture 903.

[0352] Next, the mixture 903 was placed in an alumina crucible and annealed in a muffle furnace (step S34). The annealing conditions differed for each sample, as shown in Table 3. The alumina crucible used in this example was a small, deep container as shown in container 116a in FIG. 3. 1.5 g of the sample was placed in each of these small, deep containers, and 12 of these containers were lined up in a muffle furnace and annealed. The other conditions were the same as in Example 1.

[0353] [Table 3]

[0354] <Battery cell production> Next, battery cells were fabricated in the same manner as in Example 1 using the comparative sample 4 and sample 5 obtained above.

[0355] <Measurement of charge / discharge efficiency> The cycle characteristics of the obtained battery cells of Comparative Sample 4 and Sample 5 were measured. The cycle characteristics were evaluated at 25° C. with charging as CCCV (0.2 C, 4.6 V, cut-off current 0.02 C) and discharging as CC (0.2 C, 2.5 V). The results are shown in FIG.

[0356] As shown in Figure 32, it was found that Sample 5, which was annealed with the lid on, exhibited much better cycle characteristics than Comparative Sample 4, which was annealed without the lid on. As described above, it was found that even if the O2 conditions were "flow," it was possible to prepare a positive electrode active material that exhibited good characteristics if the container was deep and the lid was placed on. [Explanation of symbols]

[0357] 101: positive electrode active material, 100A-1: positive electrode active material, 100C: positive electrode active material, 102: space inside the heating furnace, 116: container, 116a: container, 119: space, 119a: space, 120: heating furnace, 130: heating furnace, 132: belt conveyor, 134: container, 140: heating furnace, 142: material input section, 144: atmosphere control section, 146: recovery section, 200: active material layer, 201: graphene compound, 211a: positive electrode, 211b: negative electrode, 212a: lead, 212b: lead, 214: separator, 215a: joint, 215b: joint, 217: fixing member, 250: battery, 251 : exterior body, 261: folded portion, 262: sealed portion, 263: sealed portion, 271: ridge line, 272: valley line, 273: space, 300: secondary battery, 301: positive electrode can, 302: negative electrode can, 303: gasket, 304: positive electrode, 305: positive electrode current collector, 306: positive electrode active material layer, 307: negative electrode, 308: negative electrode current collector, 309: negative electrode active material layer, 310: separator, 500: secondary battery, 501: positive electrode current collector, 502: positive electrode active material layer, 503: positive electrode, 504: negative electrode current collector, 505: negative electrode active material layer, 506: negative electrode, 507: separator, 508: electrolyte, 509: exterior body, 510: Positive electrode lead electrode, 511: negative electrode lead electrode, 600: secondary battery, 601: positive electrode cap, 602: battery can, 603: positive electrode terminal, 604: positive electrode, 605: separator, 606: negative electrode, 607: negative electrode terminal, 608: insulating plate, 609: insulating plate, 611: PTC element, 612: safety valve mechanism, 613: conductive plate, 614: conductive plate, 615: module, 616: conducting wire, 617: temperature control device, 900: circuit board, 902: mixture, 902-3: mixture, 903: mixture, 903-2: mixture, 903-3: mixture, 904: positive electrode active material, 904-2: positive electrode active material, 904 -3: positive electrode active material, 904-4: positive electrode active material, 905: mixture, 908: mixture, 909: mixture, 910: label, 911: terminal, 912: circuit, 913: secondary battery, 914: antenna, 915: antenna, 916: layer, 917: layer, 918: antenna, 919: terminal, 920: display device, 921: sensor, 922: terminal, 930: housing, 930a: housing, 930b: housing, 931: negative electrode, 932: positive electrode, 933: separator, 950: wound body, 951: terminal, 952: terminal, 980: secondary battery, 981: film, 982: film, 993: wound body,994: negative electrode, 995: positive electrode, 996: separator, 997: lead electrode, 998: lead electrode, 7100: portable display device, 7101: housing, 7102: display unit, 7103: operation button, 7104: secondary battery, 7200: portable information terminal, 7201: housing, 7202: display unit, 7203: band, 7204: buckle, 7205: operation button, 7206: input / output terminal, 7207: icon, 7300: display device, 7304: display unit, 74 00: mobile phone, 7401: housing, 7402: display unit, 7403: operation button, 7404: external connection port, 7405: speaker, 7406: microphone, 7407: secondary battery, 8000: display device, 8001: housing, 8002: display unit, 8003: speaker unit, 8004: secondary battery, 8021: charging device, 8022: cable, 8024: secondary battery, 8100: lighting device, 8101: housing, 8102: light source, 8103: secondary battery, 81 04: ceiling, 8105: side wall, 8106: floor, 8107: window, 8200: indoor unit, 8201: housing, 8202: air outlet, 8203: secondary battery, 8204: outdoor unit, 8300: electric refrigerator-freezer, 8301: housing, 8302: refrigerator compartment door, 8303: freezer compartment door, 8304: secondary battery, 8400: automobile, 8401: headlight, 8406: electric motor, 8500: automobile, 8600: scooter, 8601: side mirror, 8602: Secondary battery, 8603: turn signal light, 8604: under-seat storage, 9600: tablet terminal, 9625: switch, 9626: switch, 9627: power switch, 9628: operation switch, 9629: fastener, 9630: housing, 9630a: housing, 9630b: housing, 9631: display unit, 9633: solar cell, 9634: charge / discharge control circuit, 9635: power storage unit, 9636: DCDC converter, 9637: converter, 9640: moving part,

Claims

1. forming a first mixture having a fluorine source and a magnesium source; a lid is placed on a first container containing the first mixture and the lithium cobalt oxide, and the first container is then placed in a heating furnace; After the inside of the heating furnace is made into an oxygen-containing atmosphere, the inside of the heating furnace is heated to form a composite oxide; A method for producing a positive electrode active material, comprising heating a second mixture containing the composite oxide, a nickel source, and an aluminum source, the temperature at which the second mixture is heated is lower than the temperature at which the interior of the heating furnace is heated; a space defined by the first container and the lid has an atmosphere containing a fluoride; The method for producing a positive electrode active material, wherein, in a cross-sectional view, the lid does not contact an outer side surface of the first container.

2. forming a first mixture having a fluorine source and a magnesium source; a lid is placed on a first container containing the first mixture and the lithium cobalt oxide, and the first container is then placed in a heating furnace; evacuating the inside of the heating furnace and introducing oxygen gas into the furnace, and then heating the inside of the heating furnace to form a composite oxide; A method for producing a positive electrode active material, comprising heating a second mixture containing the composite oxide, a nickel source, and an aluminum source, the temperature at which the second mixture is heated is lower than the temperature at which the interior of the heating furnace is heated; a space defined by the first container and the lid has an atmosphere containing a fluoride; The method for producing a positive electrode active material, wherein, in a cross-sectional view, the lid does not contact an outer side surface of the first container.

3. placing a lid on a first container containing a first mixture having lithium cobalt oxide, a fluorine source, and a magnesium source in a furnace; After the inside of the heating furnace is made into an oxygen-containing atmosphere, the inside of the heating furnace is heated to form a composite oxide; A method for producing a positive electrode active material, comprising heating a second mixture containing the composite oxide, a nickel source, and an aluminum source, the temperature at which the second mixture is heated is lower than the temperature at which the interior of the heating furnace is heated; a space defined by the first container and the lid has an atmosphere containing a fluoride; The method for producing a positive electrode active material, wherein, in a cross-sectional view, the lid does not contact an outer side surface of the first container.

4. placing a lid on a first container containing a first mixture having lithium cobalt oxide, a fluorine source, and a magnesium source in a furnace; evacuating the inside of the heating furnace and introducing oxygen gas into the furnace, and then heating the inside of the heating furnace to form a composite oxide; A method for producing a positive electrode active material, comprising heating a second mixture containing the composite oxide, a nickel source, and an aluminum source, the temperature at which the second mixture is heated is lower than the temperature at which the interior of the heating furnace is heated; a space defined by the first container and the lid has an atmosphere containing a fluoride; The method for producing a positive electrode active material, wherein, in a cross-sectional view, the lid does not contact an outer side surface of the first container.

5. forming a first mixture having lithium fluoride and magnesium fluoride; a lid is placed on a first container containing the first mixture and the lithium cobalt oxide, and the first container is then placed in a heating furnace; After the inside of the heating furnace is made into an oxygen-containing atmosphere, the inside of the heating furnace is heated to form a composite oxide; A method for producing a positive electrode active material, comprising heating a second mixture containing the composite oxide, a nickel source, and an aluminum source, the temperature at which the second mixture is heated is lower than the temperature at which the interior of the heating furnace is heated; a space defined by the first container and the lid has an atmosphere containing a fluoride; The method for producing a positive electrode active material, wherein, in a cross-sectional view, the lid does not contact an outer side surface of the first container.

6. forming a first mixture having lithium fluoride and magnesium fluoride; a lid is placed on a first container containing the first mixture and the lithium cobalt oxide, and the first container is then placed in a heating furnace; evacuating the inside of the heating furnace and introducing oxygen gas into the furnace, and then heating the inside of the heating furnace to form a composite oxide; A method for producing a positive electrode active material, comprising heating a second mixture containing the composite oxide, a nickel source, and an aluminum source, the temperature at which the second mixture is heated is lower than the temperature at which the interior of the heating furnace is heated; a space defined by the first container and the lid has an atmosphere containing a fluoride; The method for producing a positive electrode active material, wherein, in a cross-sectional view, the lid does not contact an outer side surface of the first container.

7. placing a lid on a first container containing a first mixture having lithium cobalt oxide, lithium fluoride, and magnesium fluoride, and then placing the first container in a heating furnace; After the inside of the heating furnace is made into an oxygen-containing atmosphere, the inside of the heating furnace is heated to form a composite oxide; A method for producing a positive electrode active material, comprising heating a second mixture containing the composite oxide, a nickel source, and an aluminum source, the temperature at which the second mixture is heated is lower than the temperature at which the interior of the heating furnace is heated; a space defined by the first container and the lid has an atmosphere containing a fluoride; The method for producing a positive electrode active material, wherein, in a cross-sectional view, the lid does not contact an outer side surface of the first container.

8. placing a lid on a first container containing a first mixture having lithium cobalt oxide, lithium fluoride, and magnesium fluoride, and then placing the first container in a heating furnace; evacuating the inside of the heating furnace and introducing oxygen gas into the furnace, and then heating the inside of the heating furnace to form a composite oxide; A method for producing a positive electrode active material, comprising heating a second mixture containing the composite oxide, a nickel source, and an aluminum source, the temperature at which the second mixture is heated is lower than the temperature at which the interior of the heating furnace is heated; a space defined by the first container and the lid has an atmosphere containing a fluoride; The method for producing a positive electrode active material, wherein, in a cross-sectional view, the lid does not contact an outer side surface of the first container.

9. 9. The method for producing a positive electrode active material according to claim 1, wherein the inside of the heating furnace is heated at 735° C. or more and 1000° C. or less.

Citation Information

Patent Citations

  • Power storage device

    JP2012018914A

  • Positive electrode active material for lithium ion secondary battery, and lithium ion secondary battery

    JP2016076454A